A high barrier puncture-resistant polyethylene composite film, preparation method and application thereof

High-barrier puncture-resistant polyethylene composite film prepared by three-layer coextrusion and bidirectional stretching processes combines modified montmorillonite, nanocellulose and boron nitride to solve the problem of insufficient barrier properties and puncture resistance of polyethylene films. , realizes high-performance polyethylene composite film.

CN118700596BActive Publication Date: 2024-12-31SHANGHAI ROYAL NEW MATERIALS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411182959.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-31
Estimated Expiration
2044-08-27

AI Technical Summary

Technical Problem

Traditional polyethylene films have poor barrier properties and puncture resistance, which cannot meet the needs of livestock and poultry pharmaceutical packaging.

Method used

The high-barrier puncture-resistant polyethylene composite film was prepared by three-layer coextrusion and bidirectional stretching process. Through the combined structure of the substrate layer, the barrier layer and the puncture-resistant layer, it uses modified montmorillonite, modified nanocellulose and modified Materials such as boron nitride improve the mechanical properties, puncture resistance and barrier properties of the film.

Benefits of technology

It significantly improves the barrier properties and puncture resistance of polyethylene composite films, improves the performance defects of traditional films, and is suitable for livestock and poultry pharmaceutical packaging and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118700596B_ABST
    Figure CN118700596B_ABST
Patent Text Reader

Abstract

The invention provides a high-barrier puncture-resistant polyethylene composite film, a preparation method and application thereof, comprising: mixing metallocene polyethylene, linear low-density polyethylene, low-density polyethylene, plasticizer, antioxidant, lubricant and ultraviolet absorber to obtain a substrate layer raw material, high-density polyethylene, modified montmorillonite, modified nanocellulose, plasticizer, dispersant and lubricant to obtain a barrier layer raw material, high-density polyethylene, maleic anhydride grafted ethylene-octene copolymer, maleic anhydride grafted polyethylene, modified boron nitride, plasticizer, dispersant and lubricant to obtain an anti-puncture layer raw material; the substrate layer raw material, the barrier layer raw material and the anti-puncture layer raw material are fed into a three-layer co-extrusion film blowing machine, extruded through a three-layer die head, and rapidly cooled to obtain a composite cast sheet, the composite cast sheet is stretched transversely and longitudinally, and after stretching, it is pulled to a winding device, and the high-barrier puncture-resistant polyethylene composite film is obtained after corona treatment and winding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of packaging films and relates to a high-barrier puncture-resistant polyethylene composite film, a preparation method and application thereof. Background Art

[0002] Polyethylene film is the most widely used type of polyolefin film material in the flexible packaging field. Due to its mature raw materials and processing technology, it is widely used in agriculture, food packaging, pharmaceutical packaging, industrial packaging and other fields.

[0003] Polyethylene raw materials are divided into high-density polyethylene, medium-density polyethylene MDPE, low-density polyethylene LDPE, and linear low-density polyethylene LLDPE according to different densities. There are also more abundant types of classifications according to the differences in catalysts, comonomers and their contents. Moreover, polyethylene films also have their own performance and application range according to different raw materials. For example, LLDPE films are used in self-adhesive films, wrapping films, cling films, etc., LDPE is mostly used in agricultural films, handbags, etc., and high-density polyethylene is mostly used in geomembranes, building films, etc.

[0004] In order to further expand the performance and application range of polyethylene film, raw material suppliers and film processors have developed biaxially oriented polyethylene film in recent years. The special polyethylene raw materials that have been polymerized and molecular structure designed are used on the biaxially oriented film production line. Through the process of melt extrusion - T-die casting - MDO longitudinal stretching - TDO transverse stretching, the cast polyethylene thick sheet is stretched into films of different thicknesses. Due to the overall 40-50 times stretching and shaping, the molecular chain is highly oriented, and the number and quality of crystals are improved, so that the film has better tensile strength, transparency and other properties, and compared with blown film and cast polyethylene film, it has better thickness uniformity and high production capacity, which is generally recognized and actively developed by processors.

[0005] The biaxially oriented polyethylene film of high-density polyethylene has high stiffness, but low impact strength, and is easy to puncture or break. The biaxially oriented polyethylene film of linear low-density polyethylene resin has high toughness and strength, but is soft and elastic, and has poor processability; the performance of each film is uneven when used alone. In addition, the barrier property of polyethylene material is poor. Generally, the water vapor permeability of polyethylene film with a thickness of 20~30μm is 5~10g / m 2 / 24h or so, when used as livestock and poultry medicine packaging, its barrier properties are not enough to meet the requirements. Summary of the invention

[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a high-barrier and puncture-resistant polyethylene composite film, a preparation method and application thereof. The present invention adopts a three-layer co-extrusion and biaxial stretching process to prepare a high-barrier and puncture-resistant polyethylene composite film with a three-layer composite structure consisting of a substrate layer, a barrier layer and an anti-puncture layer. The obtained polyethylene composite film has excellent mechanical properties, puncture resistance and barrier properties, which improves the problem of poor barrier and puncture resistance of traditional polyethylene films.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a high barrier and puncture-resistant polyethylene composite film, the preparation method comprising:

[0009] The montmorillonite is modified with hexadecyltrimethylammonium bromide and silane coupling agent in sequence to obtain modified montmorillonite;

[0010] Anhydrous lithium chloride is used to modify cellulose, and then a nanocellulose solution is prepared by TEMPO oxidation method, and finally the nanocellulose solution is amidated and modified by octadecylamine to obtain modified nanocellulose;

[0011] The hexagonal boron nitride is subjected to calcination treatment, D-xylose modification and silane coupling agent modification in sequence to obtain modified boron nitride;

[0012] The metallocene polyethylene, linear low-density polyethylene, low-density polyethylene, plasticizer, antioxidant, lubricant and ultraviolet absorber are uniformly mixed to obtain a substrate layer raw material; 70-80 parts by weight of high-density polyethylene, 12-15 parts by weight of the modified montmorillonite, 4-6 parts by weight of the modified nanocellulose, as well as a plasticizer, a dispersant and a lubricant are uniformly mixed to obtain a barrier layer raw material; 75-85 parts by weight of high-density polyethylene, 5-6 parts by weight of maleic anhydride grafted ethylene-octene copolymer, 3-4 parts by weight of maleic anhydride grafted polyethylene, 2-5 parts by weight of the modified boron nitride, as well as a plasticizer, a dispersant and a lubricant are uniformly mixed to obtain an anti-puncture layer raw material;

[0013] The substrate layer raw material, the barrier layer raw material and the puncture-resistant layer raw material are fed into a three-layer co-extrusion film blowing machine, extruded through a three-layer die head, and rapidly cooled to obtain a composite cast sheet, which is sequentially stretched transversely and longitudinally, and after stretching, is pulled to a winding device, and the high-barrier and puncture-resistant polyethylene composite film is obtained after corona treatment and winding.

[0014] The present invention adopts three-layer co-extrusion and biaxial stretching process to prepare a high-barrier and puncture-resistant polyethylene composite film with a three-layer composite structure consisting of a substrate layer, a barrier layer and an anti-puncture layer. The obtained polyethylene composite film has excellent mechanical properties, puncture resistance and barrier properties, and improves the problem of poor barrier and puncture resistance of traditional polyethylene films.

[0015] Metallocene polyethylene, linear low-density polyethylene and low-density polyethylene are used as the main materials in the substrate layer, which provides the polyethylene composite film with basic properties of high strength, high barrier and puncture resistance. Low-density polyethylene has excellent impact strength, cold resistance, low temperature resistance and high temperature resistance, but its barrier performance is poor and it is easy to age. Linear low-density polyethylene has higher flexibility, ductility and impact toughness. The molecular structure of linear low-density polyethylene is more dispersed and irregular, which makes it have higher molecular chain activity, so that it can better resist tearing and puncture. Metallocene polyethylene has excellent heat resistance, chemical stability and mechanical strength, which can enhance the firmness of the substrate layer. Metallocene polyethylene has a similar molecular structure to linear low-density polyethylene and low-density polyethylene. The compatibility of the polymer system after blending is good, which will not cause a significant decrease in the mechanical strength of the blend, and can effectively improve the fluidity of the latter. At the same time, because the three have similar molecular structures, it is easier to form a eutectic structure with similar crystallinity and crystal size. The emergence of the eutectic structure is conducive to further improving the mechanical properties of the substrate layer. In addition, after adding metallocene polyethylene to the substrate layer, the barrier properties of the polyethylene composite film have been improved to a certain extent. This is because the metallocene polyethylene molecules have good regularity and the crystals in their crystal regions are densely stacked, which leads to increased intermolecular forces, which is beneficial to improving the barrier properties of the substrate layer to moisture, thereby improving the barrier capacity of the polyethylene composite film to a certain extent.

[0016] The present invention adds modified nanocellulose and modified montmorillonite into the barrier layer, so that the internal structure of the barrier layer is more compact, forming a tortuous transmission path that can effectively hinder the diffusion of water, thereby achieving a barrier effect on water.

[0017] There are a large number of hydroxyl groups and hydrogen bonds in the nanocellulose molecular chain, which makes it show strong hydrophilicity, resulting in poor dispersibility in the polymer matrix. Nanocellulose is very easy to agglomerate in the polymer matrix, which affects its application performance in polyethylene composite films. In order to improve the interfacial compatibility and dispersibility between nanocellulose and the polymer matrix, the present invention performs hydrophobic modification on nanocellulose. First, on the basis of preparing nanocellulose by mechanochemical method, the pretreatment of N, N-dimethylacetamide / lithium chloride system is added to improve the crystallinity of cellulose, and a large number of hydroxyl groups in cellulose are exposed, which also helps the oxidizing agent to penetrate into the cellulose faster; then the hydroxyl groups on the pretreated cellulose are oxidized to carboxyl groups by TEMPO oxidation system, and the cellulose is nano-processed by high-pressure homogenization to prepare a nanocellulose solution with high carboxyl content; finally, the nanocellulose is hydrophobically modified by amidation reaction between the amino groups on octadecylamine and the carboxyl groups on nanocellulose to improve its interfacial compatibility and dispersibility with the polymer matrix.

[0018] Since cellulose molecules contain a large number of hydroxyl groups, it is very easy to form hydrogen bonds inside the cellulose molecules and between molecules. The presence of these hydrogen bonds will cause the cellulose to have a dense crystalline structure, resulting in the oxidizing agent not being easy to enter the cellulose interior and incomplete reaction. In addition, the cellulose without pretreatment is longer and has a smaller specific surface area than the cellulose after pretreatment, and the exposed hydroxyl groups are relatively few, resulting in a low carboxyl content in the nanocellulose obtained after TEMPO oxidation. In the subsequent amidation reaction process, there are fewer carboxyl groups that can react with the amino groups of octadecylamine, the degree of amidation is low, and the hydrophobic modification is insufficient. For this reason, before TEMPO oxidation treatment, the present invention first pretreats cellulose in an N, N-dimethylacetamide / lithium chloride system. The N, N-dimethylacetamide / lithium chloride system can dissolve cellulose with a larger molecular weight, promote the breaking of hydrogen bonds between cellulose molecules, destroy the crystalline structure of cellulose, expose more hydroxyl groups in the cellulose molecular chain to react with the oxidizing agent, and the carboxyl content on the pretreated cellulose obtained by oxidation is also higher.

[0019] The N,N-dimethylacetamide / lithium chloride system has a strong solubility for cellulose and can completely destroy the hydrogen bonds in cellulose. This is because N,N-dimethylacetamide contains carbonyl ions, Li + It can be tightly combined with it to form [Li(DMAc)] + Functional groups, at the same time, the free Cl - It is an active nucleophilic ion that can form hydrogen bonds with the hydroxyl groups on cellulose to destroy the hydrogen bond structure inside cellulose. Finally, Cl - With [Li(DMAc)] +Bonding, through the charge repulsion force to enhance the penetration of cellulose crystal area, so the cellulose pretreated by N, N-dimethylacetamide / lithium chloride system is more easily oxidized, and the carboxyl content in the cellulose obtained after oxidation is higher. In actual operation, the present invention first puts cellulose into N, N-dimethylacetamide for activation for a period of time, and then adds anhydrous lithium chloride for pretreatment. Such operation can reduce the amount of anhydrous lithium chloride, and the activation by N, N-dimethylacetamide can significantly weaken the interaction between cellulose molecules and destroy part of the fine structure of cellulose cells. After this treatment, TEMPO oxidation is performed, which can increase the contact area between the oxidizing agent and cellulose, and the hydrogen bond is more completely destroyed. The length of cellulose is further reduced, and the carboxyl content of the nanocellulose obtained after TEMPO oxidation is higher, which is more conducive to the amidation reaction with octadecylamine.

[0020] In the TEMPO / NaBr / NaClO oxidation system, TEMPO and sodium bromide mainly play the role of catalyst and co-catalyst, while sodium hypochlorite plays the role of main oxidant. During the oxidation process, sodium hypochlorite first oxidizes NaBr to NaBrO, and NaBrO can oxidize TEMPO to nitrogen carbonyl cation under alkaline conditions, which can first oxidize the hydroxyl group at the C6 position in cellulose to an aldehyde group, and then slowly oxidize it to a carboxyl group. Preferably, the TEMPO oxidation process is carried out under ultrasonic conditions, and ultrasound can assist cellulose oxidation to a certain extent, thereby improving the oxidation efficiency of cellulose. This is because the effect of ultrasound can cause cellulose to break, thereby increasing the specific surface area of ​​cellulose and increasing the contact probability of cellulose with the oxidizing agent; at the same time, it will also expose more hydroxyl groups in cellulose to contact with the oxidizing agent, making the oxidation more complete, and the carboxyl content in the final nanocellulose is significantly improved.

[0021] The surface hydrophilicity of montmorillonite is strong, the particle size is small, and the surface energy is high, which makes montmorillonite easy to agglomerate in the polymer matrix, significantly affecting the barrier performance advantage of montmorillonite. Therefore, the present invention sequentially uses cation exchanger intercalation modification and silane coupling agent hydrophobic modification to montmorillonite to obtain modified montmorillonite with a large interlayer spacing and surface hydrophobicity, which not only improves the dispersion uniformity and dispersion stability of montmorillonite in the polymer matrix, but also improves the barrier layer's barrier capacity to moisture by expanding its interlayer spacing.

[0022] The present invention uses hexadecyl trimethyl ammonium bromide to perform intercalation modification on montmorillonite. Hexadecyl trimethyl ammonium bromide enters the interlayer of montmorillonite through ion exchange, so that the montmorillonite lamellae are stretched open, the interlayer distance of montmorillonite is increased, the diffusion path length of water is extended, and the barrier layer's barrier ability to water is significantly improved. The organic cationic surfactant hexadecyl trimethyl ammonium bromide is used to perform organic modification on montmorillonite, which enters the interlayer of montmorillonite through ion exchange to achieve intercalation modification, but this modification method can only modify the interlayer of montmorillonite, which is beneficial to increase the interlayer distance of montmorillonite to enhance its barrier ability to water, but cannot achieve hydrophobic modification of montmorillonite, and therefore cannot significantly improve the interface compatibility between montmorillonite and the polymer matrix.

[0023] Based on this, after intercalation modification of montmorillonite, the present invention further uses a silane coupling agent to perform hydrophobic modification on the surface of the organic montmorillonite. The silane coupling agent is a type of organic silicon compound having two functional groups of different chemical properties, namely, a non-hydrolyzable functional group and a hydrolyzable functional group. The non-hydrolyzable functional group at one end, such as an epoxy group, an amino group, a vinyl functional group, etc., can react with a polyethylene resin; and the hydrolyzable functional group at the other end, namely, a siloxane functional group, can react with a hydroxyl group on the surface of the organic montmorillonite to form a silanol after hydrolysis, thereby being grafted onto the surface of the organic montmorillonite. A molecular bridge is formed between the montmorillonite and the polymer matrix through the silane coupling agent, thereby improving the interface compatibility between the montmorillonite and the polymer matrix. In addition, the silanols grafted onto the surface of the organic montmorillonite associate with each other and form partial covalent bonds after drying and dehydration, ultimately obtaining a multi-molecular hydrophobic film with a network structure that covers the surface of the organic montmorillonite, thereby changing the modified montmorillonite from hydrophilic to hydrophobic. The improvement in hydrophobicity, on the one hand, enhances the water resistance of the barrier layer and can effectively prevent water from infiltrating and penetrating the barrier layer; on the other hand, it also improves the dispersibility of montmorillonite in the polymer matrix and effectively alleviates the agglomeration of montmorillonite in the polymer matrix.

[0024] Hexagonal boron nitride has high strength and modulus, but the non-covalent interaction between boron nitride layers is strong, which makes its agglomeration tendency more serious and the dispersion degree in the polymer matrix is ​​low. The present invention calcines the hexagonal boron nitride, and then uses the liquid phase ultrasonic stripping method to modify the boron nitride. The longitudinal shearing effect of ultrasound reduces the agglomeration degree of the hexagonal boron nitride, so that the volume of the boron nitride agglomerates is significantly reduced, which is conducive to enhancing the dispersibility of the boron nitride in the polymer matrix.

[0025] The present invention uses D-xylose as a chemical modification aid and a grinding and stripping aid in the mechanical ball milling process of hydroxylated boron nitride. On the one hand, D-xylose has a tiny crystal structure. During the mechanical ball milling process, D-xylose effectively enhances the friction and pressure between the hydroxylated boron nitrides, and promotes the stripping and stratification of the hydroxylated boron nitride. The xylose-modified boron nitride obtained after stripping has a larger specific surface area, so that a larger contact area can be generated between the modified boron nitride and the polymer matrix, thereby realizing a rapid and effective transfer of the load, and enhancing the elastic modulus and yield strength of the puncture-resistant layer. In addition, the lateral size of the boron nitride modified by xylose is increased, and water needs to pass through the puncture-resistant layer. The modified boron nitride with excessively high lateral dimensions effectively increases the length of the water penetration path and gives the anti-puncture layer certain barrier properties. On the other hand, there is a valence atom remaining on the p orbital of the boron atom at the edge of the hydroxylated boron nitride, which causes the boron atom to have certain reactivity. During the mechanical ball milling process, D-xylose is in close contact with the hydroxylated boron nitride, and the reactive sites in the hydroxylated boron nitride are grafted with D-xylose. The D-xylose molecules grafted on the hydroxylated boron nitride are hydrolyzed during the washing process to generate polar functional groups such as B-OH and -NH2, which inhibit the re-deposition and aggregation of boron nitride and improve the dispersion uniformity of boron nitride in the polymer matrix.

[0026] The hydrophilicity of the boron nitride modified by D-xylose is improved, which will affect the interfacial compatibility between the xylose-modified boron nitride and the polymer matrix to a certain extent, thereby causing defects such as pores and holes between the xylose-modified boron nitride and the polymer matrix, affecting the mechanical properties of the anti-puncture layer. To this end, the present invention uses a silane coupling agent to perform surface modification on the xylose-modified boron nitride. The silane coupling agent has good amphiphilic properties, and the non-hydrolyzable functional group at one end can react with the polyethylene resin; and the siloxane functional group at the other end generates silanol after hydrolysis, which can react with the hydroxyl group on the surface of the xylose-modified boron nitride and thus be grafted to the surface of the xylose-modified boron nitride. The silane coupling agent forms a molecular bridge between the boron nitride and the polymer matrix, thereby improving the interfacial compatibility between the boron nitride and the polymer matrix, and effectively improving the defects of the boron nitride inside the polymer matrix.

[0027] In order to further improve the puncture resistance of the puncture resistance layer, the present invention adds maleic anhydride grafted polyethylene and maleic anhydride grafted ethylene-octene copolymer as compatibilizers to the puncture resistance layer to perform joint volume expansion on the polymer matrix. Maleic anhydride grafted polyethylene and maleic anhydride grafted ethylene-octene copolymer have two different action mechanisms on the interface properties between the modified boron nitride and the polymer matrix. The two cooperate with each other to produce a synergistic effect, which significantly improves the interface compatibility between the modified boron nitride and the polymer matrix, and is beneficial to simultaneously improve the strength and toughness of the puncture resistance layer.

[0028] Maleic anhydride grafted polyethylene enhances the interfacial bonding between the modified boron nitride and the polymer matrix, but the interfacial structure between the modified boron nitride and the polymer matrix is ​​rigid. The modified boron nitride is broken before relative slip occurs between the modified boron nitride and the polymer matrix, which is not conducive to improving the toughness of the puncture-resistant layer. To this end, the present invention adds maleic anhydride grafted ethylene-octene copolymer with flexible chain segments on the basis of adding maleic anhydride grafted polyethylene to adjust the interfacial force between the modified boron nitride and the polymer matrix. On the one hand, the main chain of the maleic anhydride grafted ethylene-octene copolymer is a non-polar ethylene-octene copolymer, which has good compatibility with the polymer matrix. At the same time, the ethylene-octene copolymer chain segment itself, as an elastomer, has high toughness and can dissipate a large amount of impact energy through the rotation and destruction of the ethylene-octene copolymer chain when subjected to a load. Therefore, the bonding interface between the modified boron nitride and the polymer matrix can be given good flexibility. Under the action of the load, the interface between the modified boron nitride and the polymer matrix can produce a large degree of deformation, dissipate a large amount of impact energy, and improve the tensile strength of the puncture-resistant layer while also improving its elongation at break. On the other hand, a large number of reactive hydroxyl functional groups are introduced into the boron nitride nanosheets after high temperature calcination + ultrasonic stripping + D-xylose assisted ball milling modification, which is conducive to the grafting reaction between the modified boron nitride and the anhydride functional groups on the maleic anhydride grafted ethylene-octene copolymer, thereby improving the interfacial bonding strength between the modified boron nitride and the polymer matrix. Therefore, the present invention regulates the interfacial structure between the modified boron nitride and the polymer matrix through the rigid maleic anhydride grafted polyethylene and the flexible maleic anhydride grafted ethylene-octene copolymer, thereby achieving the simultaneous improvement of the strength and toughness of the puncture-resistant layer.

[0029] As a preferred technical solution of the present invention, the modified montmorillonite is prepared by the following method:

[0030] The method comprises the following steps: dispersing montmorillonite in deionized water, ultrasonically dispersing to obtain a montmorillonite dispersion, and dripping a hydrochloric acid solution into the montmorillonite dispersion to adjust its pH value; dissolving hexadecyltrimethylammonium bromide in deionized water to obtain a modified solution, dripping the modified solution into the montmorillonite dispersion under water bath heating and mechanical stirring conditions for hydrothermal reaction, continuing stirring after all the dripping is completed, and then filtering, washing and drying to obtain an organic montmorillonite; uniformly mixing a silane coupling agent and an ethanol aqueous solution and standing to obtain a coupling agent solution, and dripping a hydrochloric acid solution into the coupling agent solution to adjust its pH value; dispersing the organic montmorillonite in the coupling agent solution, ultrasonically dispersing and heating, and then filtering, washing, drying, grinding and sieving to obtain a modified montmorillonite.

[0031] As a preferred technical solution of the present invention, the mass fraction of montmorillonite in the montmorillonite dispersion is 5~10wt%, for example, it can be 5.0wt%, 5.5wt%, 6.0wt%, 6.5wt%, 7.0wt%, 7.5wt%, 8.0wt%, 8.5wt%, 9.0wt%, 9.5wt% or 10.0wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] In some optional examples, the concentration of the hydrochloric acid solution is 0.05~0.15mol / L, for example, it can be 0.05mol / L, 0.06mol / L, 0.07mol / L, 0.08mol / L, 0.09mol / L, 0.1mol / L, 0.11mol / L, 0.12mol / L, 0.13mol / L, 0.14mol / L or 0.15mol / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] In some optional embodiments, a hydrochloric acid solution is added dropwise to the montmorillonite dispersion to adjust its pH value to 6-7, for example, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9 or 7.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] In some optional examples, the concentration of hexadecyltrimethylammonium bromide in the modified solution is 0.4~0.5g / mL, for example, it can be 0.4g / mL, 0.41g / mL, 0.42g / mL, 0.43g / mL, 0.44g / mL, 0.45g / mL, 0.46g / mL, 0.47g / mL, 0.48g / mL, 0.49g / mL or 0.5g / mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] In some optional examples, the mass ratio of hexadecyltrimethylammonium bromide in the modified solution to montmorillonite in the montmorillonite dispersion is 1:(3~4), for example, it can be 1:3.0, 1:3.1, 1:3.2, 1:3.3, 1:3.4, 1:3.5, 1:3.6, 1:3.7, 1:3.8, 1:3.9 or 1:4.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] The present invention particularly limits the mass ratio of hexadecyltrimethylammonium bromide to montmorillonite to be 1:(3~4), and with the increase of the consumption of hexadecyltrimethylammonium bromide, the interlayer distance of montmorillonite increases rapidly, then gradually slows down, and finally tends to be stable. This is because, when the consumption of hexadecyltrimethylammonium bromide is less, the cation exchange between montmorillonite lamellae has not yet reached exchange saturation, and therefore, the interlayer distance of montmorillonite is relatively small, and the barrier effect of the lamellar structure on moisture cannot be effectively exerted. With the increase of hexadecyltrimethylammonium bromide, the interlayer distance of montmorillonite increases rapidly, and when the mass ratio of hexadecyltrimethylammonium bromide to montmorillonite reaches the upper limit of the range defined by the present invention, the ion exchange between montmorillonite lamellae tends to be saturated, and at this time, the consumption of hexadecyltrimethylammonium bromide continues to be increased, and the interlayer distance of montmorillonite will not increase significantly either, therefore, considering the processing cost, the present invention particularly limits the mass ratio of hexadecyltrimethylammonium bromide to montmorillonite to be 1:(3~4).

[0037] In some optional examples, the temperature of the hydrothermal reaction of the modified solution and the montmorillonite dispersion is 70-80°C, for example, it can be 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] The present invention particularly limits the temperature of the hydrothermal reaction of the modified solution and the montmorillonite dispersion to 70-80°C. When the hydrothermal reaction temperature is lower than 70°C, the reaction activity of hexadecyltrimethylammonium bromide is low and the reaction rate is slow, resulting in insufficient ion exchange between montmorillonite layers. As the hydrothermal reaction temperature increases, the reaction activity of hexadecyltrimethylammonium bromide increases, which is beneficial to the ion exchange between the organic cation and the montmorillonite layer. When the heating temperature is higher than 80°C, the interlayer spacing of the montmorillonite will show a downward trend. This is because the excessively high temperature is not conducive to the negative charge between the hexadecyltrimethylammonium bromide and the montmorillonite layer to reach an electrostatic balance, so that the hexadecyltrimethylammonium bromide intercalated into the montmorillonite layer is dissociated again, resulting in a decrease in the interlayer spacing of the montmorillonite.

[0039] In some optional examples, after all the modified solution is dropped into the montmorillonite dispersion, stirring is continued for 1.5 to 2.5 hours, for example, 1.5 hours, 1.6 hours, 1.7 hours, 1.8 hours, 1.9 hours, 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours or 2.5 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0040] In some optional examples, the mass fraction of the silane coupling agent in the coupling agent solution is 5-10wt%, for example, it can be 5.0wt%, 5.5wt%, 6.0wt%, 6.5wt%, 7.0wt%, 7.5wt%, 8.0wt%, 8.5wt%, 9.0wt%, 9.5wt% or 10.0wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] In some optional examples, the volume ratio of ethanol to deionized water in the ethanol aqueous solution is (8~9):(1~2), for example, it can be 8:2, 8.1:1.9, 8.2:1.8, 8.3:1.7, 8.4:1.6, 8.5:1.5, 8.6:1.4, 8.7:1.3, 8.8:1.2, 8.9:1.1 or 9.0:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0042] In some optional embodiments, hydrochloric acid solution is added dropwise to the coupling agent solution to adjust its pH value to 4-5, for example, it can be 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9 or 5.0, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] In some optional examples, the mass ratio of the organic montmorillonite to the silane coupling agent in the coupling agent solution is 1:(0.4~0.5), for example, it can be 1:0.4, 1:0.41, 1:0.42, 1:0.43, 1:0.44, 1:0.45, 1:0.46, 1:0.47, 1:0.48, 1:0.49 or 1:0.5, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] In some optional examples, the heating temperature of the organic montmorillonite and the coupling agent solution during ultrasonic dispersion is 80-90°C, for example, it can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0045] In some optional examples, the heating time of the organic montmorillonite and the coupling agent solution during ultrasonic dispersion is 2 to 3 hours, for example, it can be 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours, 2.5 hours, 2.6 hours, 2.7 hours, 2.8 hours, 2.9 hours or 3.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0046] In some optional examples, the mesh size of the sieve used for screening is 200-300 mesh, for example, it can be 200 mesh, 210 mesh, 220 mesh, 230 mesh, 240 mesh, 250 mesh, 260 mesh, 270 mesh, 280 mesh, 290 mesh or 300 mesh, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] As a preferred technical solution of the present invention, the modified nanocellulose is prepared by the following method:

[0048] The cellulose is dispersed in N,N-dimethylacetamide, stirred and heated to obtain a cellulose dispersion, anhydrous lithium chloride is added to the cellulose dispersion, stirred and heated to react, and then filtered, washed and freeze-dried for the first time to obtain pretreated cellulose; the pretreated cellulose is dispersed in deionized water to obtain a cellulose suspension, TEMPO and sodium bromide are added to the cellulose suspension, mixed evenly to obtain a precursor solution, sodium hypochlorite solution is added dropwise to the precursor solution to cause an oxidation reaction, a product solution is obtained after the reaction is completed, and the product solution is subjected to high-pressure homogenization to obtain a nanocellulose solution; the nanocellulose solution is mixed with an octadecylamine solution, stirred and heated to cause an amidation reaction, and then centrifuged, washed and freeze-dried for the second time to obtain modified nanocellulose.

[0049] As a preferred technical solution of the present invention, the ratio of cellulose to N,N-dimethylacetamide is (0.01~0.03) g:1mL, for example, it can be 0.01g:1mL, 0.012g:1mL, 0.014g:1mL, 0.016g:1mL, 0.018g:1mL, 0.02g:1mL, 0.022g:1mL, 0.024g:1mL, 0.026g:1mL, 0.028g:1mL or 0.03g:1mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] In some optional examples, the heating temperature when the cellulose and N,N-dimethylacetamide are mixed is 140-150°C, for example, it can be 140°C, 141°C, 142°C, 143°C, 144°C, 145°C, 146°C, 147°C, 148°C, 149°C or 150°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0051] In some optional examples, the stirring time when the cellulose and N,N-dimethylacetamide are mixed is 2 to 3 hours, for example, it can be 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours, 2.5 hours, 2.6 hours, 2.7 hours, 2.8 hours, 2.9 hours or 3.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0052] In some optional examples, the ratio of N,N-dimethylacetamide to anhydrous lithium chloride in the cellulose dispersion is 1mL:(0.06~0.08)g, for example, it can be 1mL:0.06g, 1mL:0.062g, 1mL:0.064g, 1mL:0.066g, 1mL:0.068g, 1mL:0.07g, 1mL:0.072g, 1mL:0.074g, 1mL:0.076g, 1mL:0.078g or 1mL:0.08g, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0053] In some optional examples, the heating temperature when the cellulose dispersion is mixed with anhydrous lithium chloride is 80-100°C, for example, it can be 80°C, 82°C, 84°C, 86°C, 88°C, 90°C, 92°C, 94°C, 96°C, 98°C or 100°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0054] In some optional examples, the stirring time when the cellulose dispersion is mixed with anhydrous lithium chloride is 1 to 2 hours, for example, it can be 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] In some optional examples, the first freeze-drying temperature is -40~-50°C, for example, it can be -40°C, -41°C, -42°C, -43°C, -44°C, -45°C, -46°C, -47°C, -48°C, -49°C or -50°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0056] In some optional examples, the first freeze-drying time is 12 to 24 hours, for example, it can be 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0057] In some optional examples, the concentration of the pretreated cellulose in the cellulose suspension is 0.01~0.012 g / mL, for example, it can be 0.01 g / mL, 0.0102 g / mL, 0.0104 g / mL, 0.0106 g / mL, 0.0108 g / mL, 0.011 g / mL, 0.0112 g / mL, 0.0114 g / mL, 0.0116 g / mL, 0.0118 g / mL or 0.012 g / mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0058] In some optional examples, the mass ratio of the pretreated cellulose, the TEMPO and the sodium bromide in the cellulose suspension is 1:(0.06~0.08):(0.2~0.3), for example, it can be 1:0.06:0.2, 1:0.062:0.21, 1:0.064:0.22, 1:0.066:0.23, 1:0.068:0.24, 1:0.07:0.25, 1:0.072:0.26, 1:0.074:0.27, 1:0.076:0.28, 1:0.078:0.29 or 1:0.08:0.3, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0059] In some optional examples, the concentration of the sodium hypochlorite solution is 0.3-0.5 g / mL, for example, it can be 0.3 g / mL, 0.32 g / mL, 0.34 g / mL, 0.36 g / mL, 0.38 g / mL, 0.4 g / mL, 0.42 g / mL, 0.44 g / mL, 0.46 g / mL, 0.48 g / mL or 0.5 g / mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0060] In some optional examples, the mass ratio of the pretreated cellulose in the precursor solution to the sodium hypochlorite in the sodium hypochlorite solution is 1:(5~8), for example, it can be 1:5.0, 1:5.2, 1:5.4, 1:5.6, 1:5.8, 1:6.0, 1:6.2, 1:6.4, 1:6.6, 1:6.8, 1:7.0, 1:7.2, 1:7.4, 1:7.6, 1:7.8 or 1:8.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0061] In some optional examples, during the oxidation reaction, an alkali solution with a concentration of 0.1 mol / L is added to the precursor solution to control its pH value at 10-11, for example, 10, 10.1, 10.2, 10.3, 10.4, 10.5, 10.6, 10.7, 10.8, 10.9 or 11, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0062] In some optional examples, the oxidation reaction time is 4 to 5 hours, for example, it can be 4.0 hours, 4.1 hours, 4.2 hours, 4.3 hours, 4.4 hours, 4.5 hours, 4.6 hours, 4.7 hours, 4.8 hours, 4.9 hours or 5.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0063] In some optional instances, the pressure of the high-pressure homogenization is 70~80MPa, for example, it can be 70MPa, 71MPa, 72MPa, 73MPa, 74MPa, 75MPa, 76MPa, 77MPa, 78MPa, 79MPa or 80MPa, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0064] In some optional examples, the number of high-pressure homogenization is 5 to 8 times, for example, 5 times, 6 times, 7 times or 8 times, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0065] In some optional examples, the mass fraction of the nanocellulose solution is 0.5~1.5wt%, for example, it can be 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt% or 1.5wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0066] In some optional examples, the octadecylamine solution is composed of octadecylamine and an ethanol aqueous solution, wherein the volume ratio of ethanol to deionized water in the ethanol aqueous solution is (7~9):(1~3), for example, it can be 7:3, 7.2:2.8, 7.4:2.6, 7.6:2.4, 7.8:2.2, 8:2, 8.2:1.8, 8.4:1.6, 8.6:1.4, 8.8:1.2 or 9:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0067] In some optional examples, the mass fraction of octadecylamine in the octadecylamine solution is 2-4 g / L, for example, it can be 2.0 g / L, 2.2 g / L, 2.4 g / L, 2.6 g / L, 2.8 g / L, 3.0 g / L, 3.2 g / L, 3.4 g / L, 3.6 g / L, 3.8 g / L or 4.0 g / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0068] In some optional examples, the mass ratio of pure dry nanocellulose in the nanocellulose solution to octadecylamine in the octadecylamine solution is (2~3):1, for example, it can be 2.0:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1 or 3.0:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0069] The present invention particularly limits the mass ratio of the pure dry nanocellulose in the nanocellulose solution and the octadecylamine in the octadecylamine solution to be (2-3): 1, and the consumption of octadecylamine can directly affect the hydrophobicity of the modified nanocellulose, and then affect the interfacial compatibility between the modified nanocellulose and the polymer matrix. Along with the increase of the consumption of octadecylamine, the hydrophobicity of the modified nanocellulose is a trend of change that first increases and then decreases, and this is due to the amidation reaction of the amino group on the octadecylamine molecular chain and the carboxyl group on the nanocellulose molecular chain, so that the octadecylamine molecular chain is grafted on the nanocellulose, thereby improving the hydrophobicity of the modified nanocellulose. But when the consumption of octadecylamine exceeds the upper limit of the range limited by the present invention, too much octadecylamine molecular long chain is with-NH2 as the core is entangled, hindering the occurrence of amidation reaction, causing the hydrophobicity of the modified nanocellulose to reduce.

[0070] In some optional examples, the heating temperature when the nanocellulose solution and the octadecylamine solution are mixed is 55-65°C, for example, it can be 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C or 65°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0071] In some optional examples, the stirring time when the nanocellulose solution and the octadecylamine solution are mixed is 3 to 5 hours, for example, it can be 3.0 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours, 4.0 hours, 4.2 hours, 4.4 hours, 4.6 hours, 4.8 hours or 5.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0072] In some optional examples, the temperature of the second freeze-drying is -40~-50°C, for example, it can be -40°C, -41°C, -42°C, -43°C, -44°C, -45°C, -46°C, -47°C, -48°C, -49°C or -50°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0073] In some optional examples, the second freeze-drying time is 12 to 24 hours, for example, it can be 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0074] As a preferred technical solution of the present invention, the modified boron nitride is prepared by the following method:

[0075] Hexagonal boron nitride is calcined to obtain calcined boron nitride, the calcined boron nitride is dispersed in deionized water to form a boron nitride dispersion, the boron nitride dispersion is ultrasonically stripped, and then filtered, washed and dried to obtain hydroxylated boron nitride; the hydroxylated boron nitride and D-xylose are mixed and ball-milled to obtain a composite powder, the composite powder is dispersed in deionized water to form a powder dispersion, the powder dispersion is centrifuged, and the precipitate is dried to obtain xylose-modified boron nitride; the xylose-modified boron nitride is immersed in a silane coupling agent solution and heated, and then filtered, washed and dried to obtain modified boron nitride.

[0076] As a preferred technical solution of the present invention, the calcination temperature of the hexagonal boron nitride is 800-900°C, for example, it can be 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C or 900°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0077] In some optional examples, the heating rate of the hexagonal boron nitride during calcination is 10-20°C / min, for example, it can be 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min, 15°C / min, 16°C / min, 17°C / min, 18°C / min, 19°C / min or 20°C / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0078] In some optional examples, the holding time of the hexagonal boron nitride during calcination is 30 to 40 minutes, for example, it can be 30 minutes, 31 minutes, 32 minutes, 33 minutes, 34 minutes, 35 minutes, 36 minutes, 37 minutes, 38 minutes, 39 minutes or 40 minutes, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0079] In some optional examples, the ratio of the calcined boron nitride and deionized water when mixed is 1g:(100~120)mL, for example, it can be 1g:100mL, 1g:102mL, 1g:104mL, 1g:106mL, 1g:108mL, 1g:110mL, 1g:112mL, 1g:114mL, 1g:116mL, 1g:118mL or 1g:120mL, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0080] In some optional examples, the ultrasonic power of the ultrasonic stripping of the boron nitride dispersion is 200~300W, for example, it can be 200W, 210W, 220W, 230W, 240W, 250W, 260W, 270W, 280W, 290W or 300W, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0081] In some optional examples, the ultrasonic stripping time of the boron nitride dispersion is 1 to 2 hours, for example, 1.0 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h or 2.0 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0082] In some optional examples, the mass ratio of the hydroxylated boron nitride to the D-xylose is 1:(0.15~0.25), for example, it can be 1:0.15, 1:0.16, 1:0.17, 1:0.18, 1:0.19, 1:0.2, 1:0.21, 1:0.22, 1:0.23, 1:0.24 or 1:0.25, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0083] In some optional examples, the rotation speed of the mixed ball milling of the hydroxylated boron nitride and D-xylose is 150-250 r / min, for example, it can be 150 r / min, 160 r / min, 170 r / min, 180 r / min, 190 r / min, 200 r / min, 210 r / min, 220 r / min, 230 r / min, 240 r / min or 250 r / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0084] In some optional examples, the time for mixing the hydroxylated boron nitride and D-xylose for ball milling is 10 to 12 hours, for example, 10.0 hours, 10.2 hours, 10.4 hours, 10.6 hours, 10.8 hours, 11.0 hours, 11.2 hours, 11.4 hours, 11.6 hours, 11.8 hours or 12.0 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0085] In some optional examples, the mass fraction of the composite powder in the powder dispersion is 0.5~1.5wt%, for example, it can be 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt% or 1.5wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0086] In some optional examples, the silane coupling agent solution consists of a silane coupling agent and an ethanol aqueous solution.

[0087] In some optional examples, the mass fraction of the silane coupling agent in the silane coupling agent solution is 5-6wt%, for example, 5.0wt%, 5.1wt%, 5.2wt%, 5.3wt%, 5.4wt%, 5.5wt%, 5.6wt%, 5.7wt%, 5.8wt%, 5.9wt% or 6.0wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0088] In some optional examples, the immersion time of the xylose-modified boron nitride in the silane coupling agent solution is 3 to 5 hours, for example, it can be 3.0 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours, 4.0 hours, 4.2 hours, 4.4 hours, 4.6 hours, 4.8 hours or 5.0 hours, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0089] In some optional examples, the heating temperature of the xylose-modified boron nitride when immersed in the silane coupling agent solution is 50-60°C, for example, it can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0090] As a preferred technical solution of the present invention, the maleic anhydride grafting rate of the maleic anhydride grafted polyethylene is 5-8%, for example, it can be 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5% or 8.0%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0091] In some optional examples, the maleic anhydride grafting rate of the maleic anhydride grafted ethylene-octene copolymer is 10-15%, for example, it can be 10.0%, 10.5%, 11.0%, 11.5%, 12.0%, 12.5%, 13.0%, 13.5%, 14.0%, 14.5% or 15.0%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0092] In some optional examples, the mass ratio of the substrate layer raw material, the barrier layer raw material and the puncture-resistant layer raw material is 1:(1.5~2.5):(1.5~2.5), for example, it can be 1:1.5:1.5, 1:1.6:1.6, 1:1.7:1.7, 1:1.8:1.8, 1:1.9:1.9, 1:2:2, 1:2.1:2.1, 1:2.2:2.2, 1:2.3:2.3, 1:2.4:2.4 or 1:2.5:2.5, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0093] In some optional examples, the three-layer co-extrusion film blowing machine includes three groups of single-screw extruders, and the substrate layer raw material, the barrier layer raw material and the anti-puncture layer raw material are fed from different single-screw extruders respectively.

[0094] In some optional examples, the barrel of the single-screw extruder is divided into a first zone, a second zone, a third zone, a fourth zone and a fifth zone with different temperatures along the material flow direction.

[0095] In some optional instances, the temperature of the first zone is 160-170°C, for example, it may be 160°C, 161°C, 162°C, 163°C, 164°C, 165°C, 166°C, 167°C, 168°C, 169°C or 170°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0096] In some optional instances, the temperature of the second zone is 165-175°C, for example, it can be 165°C, 166°C, 167°C, 168°C, 169°C, 170°C, 171°C, 172°C, 173°C, 174°C or 175°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0097] In some optional instances, the temperature of the third zone is 170-180°C, for example, it may be 170°C, 171°C, 172°C, 173°C, 174°C, 175°C, 176°C, 177°C, 178°C, 179°C or 180°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0098] In some optional instances, the temperature of the fourth zone is 180-190°C, for example, it can be 180°C, 181°C, 182°C, 183°C, 184°C, 185°C, 186°C, 187°C, 188°C, 189°C or 190°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0099] In some optional instances, the temperature of the fifth zone is 175-185°C, for example, it can be 175°C, 176°C, 177°C, 178°C, 179°C, 180°C, 181°C, 182°C, 183°C, 184°C or 185°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0100] In some optional embodiments, the temperature of the transverse stretching is 120-130°C, for example, it can be 120°C, 121°C, 122°C, 123°C, 124°C, 125°C, 126°C, 127°C, 128°C, 129°C or 130°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0101] In some optional embodiments, the stretch ratio of the transverse stretching is 7 to 10, for example, it can be 7.0, 7.2, 7.4, 7.6, 7.8, 8.0, 8.2, 8.4, 8.6, 8.8, 9.0, 9.2, 9.4, 9.6, 9.8 or 10.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0102] In some optional embodiments, the temperature of the longitudinal stretching is 110-120°C, for example, it can be 110°C, 111°C, 112°C, 113°C, 114°C, 115°C, 116°C, 117°C, 118°C, 119°C or 120°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0103] In some optional embodiments, the stretch ratio of the longitudinal stretching is 4 to 6, for example, it can be 4.0, 4.2, 4.4, 4.6, 4.8, 5.0, 5.2, 5.4, 5.6, 5.8 or 6.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0104] In a second aspect, the present invention provides a high barrier and puncture resistant polyethylene composite film prepared by the preparation method described in the first aspect, wherein the high barrier and puncture resistant polyethylene composite film comprises a substrate layer, a barrier layer and a puncture resistant layer stacked in sequence.

[0105] The substrate layer comprises metallocene polyethylene, linear low-density polyethylene, low-density polyethylene, a plasticizer, an antioxidant, a lubricant and an ultraviolet absorber.

[0106] The barrier layer comprises high-density polyethylene, modified montmorillonite, modified nanocellulose, a plasticizer, a dispersant and a lubricant.

[0107] The puncture-resistant layer comprises high-density polyethylene, maleic anhydride grafted ethylene-octene copolymer, maleic anhydride grafted polyethylene, modified boron nitride, a plasticizer, a dispersant and a lubricant.

[0108] As a preferred technical solution of the present invention, the thickness of the substrate layer is 10~20μm, for example, it can be 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, 19μm or 20μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0109] In some optional examples, the thickness of the barrier layer is 20-30 μm, for example, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, 26 μm, 27 μm, 28 μm, 29 μm or 30 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0110] In some optional examples, the thickness of the puncture-resistant layer is 20-30 μm, for example, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, 26 μm, 27 μm, 28 μm, 29 μm or 30 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0111] In some optional examples, the total thickness of the high barrier puncture resistant polyethylene composite film is 60-80 μm, for example, it can be 60 μm, 62 μm, 64 μm, 66 μm, 68 μm, 70 μm, 72 μm, 74 μm, 76 μm, 78 μm or 80 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0112] As a preferred technical solution of the present invention, the substrate layer comprises the following components in parts by weight:

[0113] 50-60 parts of metallocene polyethylene;

[0114] 15-25 parts of linear low-density polyethylene;

[0115] 10-20 parts of low-density polyethylene;

[0116] 3~5 parts of plasticizer;

[0117] 0.5~1.5 parts of antioxidant;

[0118] Lubricant 0.8~1.2 parts;

[0119] 0.3~0.8 parts of UV absorber.

[0120] The weight proportion of the metallocene polyethylene can be 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 55 parts, 56 parts, 57 parts, 58 parts, 59 parts or 60 parts; the weight proportion of the linear low density polyethylene can be 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts or 25 parts; the weight proportion of the low density polyethylene can be 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts; the weight proportion of the plasticizer can be 3.0 parts, 3.2 parts, 3.4 parts, 3.6 parts, 3.8 parts, 4.0 parts, 4.2 parts, 4.4 parts, 4.6 parts, 4.8 parts or 5.0 parts by weight; the weight parts of the antioxidant can be 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1.0 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts or 1.5 parts; the weight parts of the lubricant can be 0.8 parts, 0.85 parts, 0.9 parts, 0.95 parts, 1.0 parts, 1.05 parts, 1.1 parts, 1.15 parts or 1.2 parts; the weight parts of the ultraviolet absorber can be 0.3 parts, 0.35 parts, 0.4 parts, 0.45 parts, 0.5 parts, 0.55 parts, 0.6 parts, 0.65 parts, 0.7 parts, 0.75 parts or 0.8 parts, but are not limited to the listed values, and other values ​​not listed within the numerical range are equally applicable.

[0121] In some optional examples, the barrier layer includes the following components in parts by weight:

[0122] High-density polyethylene 70-80 parts;

[0123] Modified montmorillonite 12-15 parts;

[0124] 4-6 parts of modified nanocellulose;

[0125] 2~5 parts of plasticizer;

[0126] Dispersant 1~3 parts;

[0127] Lubricant 0.8~1.2 parts.

[0128] Wherein, the weight portion of high density polyethylene can be 70 parts, 71 parts, 72 parts, 73 parts, 74 parts, 75 parts, 76 parts, 77 parts, 78 parts, 79 parts or 80 parts; the weight portion of modified montmorillonite can be 12 parts, 12.2 parts, 12.4 parts, 12.6 parts, 12.8 parts, 13 parts, 13.2 parts, 13.4 parts, 13.6 parts, 13.8 parts, 14 parts, 14.2 parts, 14.4 parts, 14.6 parts, 14.8 parts or 15 parts; the weight portion of modified nanocellulose can be 4.0 parts, 4.2 parts, 4.4 parts, 4.6 parts, 4.8 parts, 5.0 parts, 5.2 parts, 5.4 parts, 5 .6, 5.8 or 6.0 parts by weight; the weight portion of the plasticizer can be 2.0, 2.5, 3.0, 3.5, 4.0, 4.5 or 5.0 parts; the weight portion of the dispersant can be 1.0, 1.2, 1.4, 1.6, 1.8, 2.0, 2.2, 2.4, 2.6, 2.8 or 3.0 parts; the weight portion of the lubricant can be 0.8, 0.85, 0.9, 0.95, 1.0, 1.05, 1.1, 1.15 or 1.2 parts, but is not limited to the listed values, and other values ​​not listed within the numerical range are equally applicable.

[0129] The present invention adds 12 to 15 parts of modified montmorillonite and 4 to 6 parts of modified nanocellulose to the barrier layer. The modified montmorillonite and the modified nanocellulose produce a synergistic effect, which can extend the diffusion path of water in the barrier layer. However, excessive montmorillonite and excessive modified nanocellulose will agglomerate in the barrier layer, thereby affecting the barrier capacity of the barrier layer.

[0130] In addition, when the amount of modified montmorillonite exceeds 15 parts, the transmittance of the barrier layer will be affected to a certain extent. This is because the amount of modified montmorillonite is too high, which causes the modified montmorillonite to agglomerate in the barrier layer. The refractive index of montmorillonite is greater than that of the polymer matrix. The modified montmorillonite agglomerates increase the number of light scattering interfaces inside the barrier layer, and the refractive index of the air in the gap of the modified nanocellulose is quite different from that of the modified montmorillonite, resulting in the maximum scattering of light when passing through the barrier layer, thereby having a negative impact on the transparency of the barrier layer.

[0131] In some optional examples, the puncture-resistant layer includes the following components in parts by weight:

[0132] High-density polyethylene 75-85 parts;

[0133] 5-6 parts of maleic anhydride grafted ethylene-octene copolymer;

[0134] 3-4 parts of maleic anhydride grafted polyethylene;

[0135] Modified boron nitride 2-5 parts;

[0136] 2~5 parts of plasticizer;

[0137] Dispersant 1~3 parts;

[0138] Lubricant 0.8~1.2 parts.

[0139] The weight proportion of high density polyethylene can be 75, 76, 77, 78, 79, 80, 81, 82, 83, 84 or 85 parts; the weight proportion of maleic anhydride grafted ethylene-octene copolymer can be 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9 or 6.0 parts; the weight proportion of maleic anhydride grafted polyethylene can be 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9 or 4.0 parts; the weight proportion of modified boron nitride can be 2.0, 2.5, 3.9, 4.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9 or 6.0 parts. The weight parts of the plasticizer can be 2.0 parts, 2.5 parts, 3.0 parts, 3.5 parts, 4.0 parts, 4.5 parts or 5.0 parts; the weight parts of the dispersant can be 1.0 parts, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, 2.0 parts, 2.2 parts, 2.4 parts, 2.6 parts, 2.8 parts or 3.0 parts; the weight parts of the lubricant can be 0.8 parts, 0.85 parts, 0.9 parts, 0.95 parts, 1.0 parts, 1.05 parts, 1.1 parts, 1.15 parts or 1.2 parts, but are not limited to the listed values, and other values ​​not listed within the numerical range are equally applicable.

[0140] The present invention adds 5 to 6 parts of maleic anhydride grafted ethylene-octene copolymer and 3 to 4 parts of maleic anhydride grafted polyethylene to the puncture-resistant layer, so that the puncture-resistant layer has excellent tensile strength and elongation at break. This is because the addition of maleic anhydride grafted ethylene-octene copolymer ensures the interface compatibility between the modified boron nitride and the polymer matrix, and the flexible chain of the ethylene-octene copolymer avoids the strong stress concentration on the surface of the modified boron nitride when the puncture-resistant layer is subjected to a load, so that the interface between the modified boron nitride and the polymer matrix can be greatly deformed, effectively improving the elongation at break of the puncture-resistant layer, and it is precisely because of this large deformation that the strain hardening of the puncture-resistant layer is caused, so that the tensile strength of the puncture-resistant layer can also be significantly improved. However, when the addition amount of maleic anhydride grafted ethylene-octene copolymer exceeds 6 parts, the tensile strength of the puncture-resistant layer will show a downward trend. This is because the ethylene-octene copolymer chain segment in the maleic anhydride grafted ethylene-octene copolymer is a flexible chain with a lower modulus. Therefore, when the addition amount of maleic anhydride grafted ethylene-octene copolymer is too high, the tensile strength of the puncture-resistant layer will show a downward trend.

[0141] The present invention specifically limits the addition amount of modified boron nitride in the puncture-resistant layer to 2 to 5 parts. After adding an appropriate amount of modified boron nitride to the puncture-resistant layer, the tensile strength and elongation at break of the prepared puncture-resistant layer can also be improved to a certain extent. When the addition amount of modified boron nitride exceeds 5 parts, the tensile strength of the puncture-resistant layer hardly changes. This is because the non-covalent interaction between the modified boron nitride nanosheets is strong. When the addition amount of modified boron nitride in the puncture-resistant layer is large, agglomeration is likely to occur. The generation of modified boron nitride agglomerates will lead to a weakening of the interfacial bonding between the modified boron nitride and the polymer matrix. Therefore, the tensile strength of the puncture-resistant layer cannot be further improved.

[0142] In addition, when the addition amount of modified boron nitride exceeds 5 parts, the elongation at break of the puncture-resistant layer will show a downward trend. This is because the addition amount of modified boron nitride is too much, which affects the dispersion uniformity of modified boron nitride in the polymer matrix, aggravates the agglomeration tendency of modified boron nitride, and forms defects inside the polymer matrix, making the internal stress distribution of the puncture-resistant layer uneven under the action of load, which is easy to produce local stress concentration, and first induce cracks at the stress concentration site, accelerating the destruction of the puncture-resistant layer, thereby reducing the elongation at break of the puncture-resistant layer.

[0143] In some optional examples, the ultraviolet absorber is any one of UV-531, UV-326 or UV-234, or a combination of at least two of them.

[0144] In some optional examples, the antioxidant is any one of antioxidant 1010, antioxidant 1076, antioxidant 626, antioxidant 168, or a combination of at least two thereof.

[0145] In some optional examples, the dispersant is any one of liquid paraffin, silicone oil, and ethylene glycol, or a combination of at least two of them.

[0146] In some optional examples, the lubricant is any one of stearic acid, zinc stearate, calcium stearate, or a combination of at least two thereof.

[0147] In some optional examples, the plasticizer is any one of glycerol, epoxidized soybean oil, paraffin oil, or a combination of at least two thereof.

[0148] In a third aspect, the present invention provides a use of the high barrier and puncture-resistant polyethylene composite film described in the second aspect in livestock and poultry medicine packaging.

[0149] Compared with the prior art, the present invention has the following beneficial effects:

[0150] The present invention adopts three-layer co-extrusion and biaxial stretching process to prepare a high-barrier and puncture-resistant polyethylene composite film with a three-layer composite structure consisting of a substrate layer, a barrier layer and an anti-puncture layer. The obtained polyethylene composite film has excellent mechanical properties, puncture resistance and barrier properties, and improves the problem of poor barrier and puncture resistance of traditional polyethylene films. BRIEF DESCRIPTION OF THE DRAWINGS

[0151] Figure 1 A process flow chart for preparing a high barrier and puncture resistant polyethylene composite film provided in Examples 1-13 of the present invention;

[0152] Figure 2 The XRD diagrams of the unmodified montmorillonite and the modified montmorillonite prepared in Example 1 of the present invention after being jointly modified by hexadecyltrimethylammonium bromide and a silane coupling agent;

[0153] Figure 3 This is a scanning electron microscope image of the nanocellulose solution prepared in Example 1 of the present invention at a low magnification;

[0154] Figure 4 This is a scanning electron microscope image of the nanocellulose solution prepared in Example 1 of the present invention at a high magnification;

[0155] Figure 5 This is a scanning electron microscope image of the modified nanocellulose prepared in Example 1 of the present invention at a low magnification;

[0156] Figure 6 This is a scanning electron microscope image of the modified nanocellulose prepared in Example 1 of the present invention at a high magnification;

[0157] Figure 7 The infrared spectra of octadecylamine, the nanocellulose solution prepared in Example 1 of the present invention that is not modified by octadecylamine amidation, and the modified nanocellulose that is modified by octadecylamine amidation;

[0158] Figure 8 This is a scanning electron microscope image of the hydroxylated boron nitride prepared in Example 1 of the present invention;

[0159] Fig. 9 This is a scanning electron microscope image of the xylose-modified boron nitride prepared in Example 1 of the present invention;

[0160] Fig.10 This is a scanning electron microscope image of the tensile section of the puncture-resistant layer prepared in Example 1 of the present invention;

[0161] Fig.11 This is a scanning electron microscope image of the tensile cross-section of the puncture-resistant layer prepared in Comparative Example 8 of the present invention. DETAILED DESCRIPTION

[0162] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.

[0163] The chemical reagents used in the specific embodiments of the present invention are all commercially available products, and their brands, specifications, manufacturers and other information are as follows:

[0164] Montmorillonite: S42017-100g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0165] Hydrochloric acid: industrial grade, purchased from Nanjing Chemical Reagent Co., Ltd.;

[0166] Hexadecyltrimethylammonium bromide: S15001-100g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0167] Coupling agent KH540: industrial grade, purity ≥99%, purchased from Wuhan Proloff Biotechnology Co., Ltd.;

[0168] Coupling agent KH550: S15028-500ml, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0169] Coupling agent KH560: S15029-500ml, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0170] Coupling agent KH570: S15030-500ml, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0171] Coupling agent KH792: industrial grade, purity ≥99%, purchased from Jinan Luxin Chemical Co., Ltd.;

[0172] Anhydrous ethanol: industrial grade, purity ≥99%, purchased from Nanjing Chemical Reagent Co., Ltd.;

[0173] Cellulose: S14009-250 g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0174] N,N-dimethylacetamide: S27119-500ml, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0175] Anhydrous lithium chloride: industrial grade, purity ≥97%, purchased from Fuchen (Tianjin) Chemical Reagent Co., Ltd.;

[0176] TEMPO: T832402, purchased from Wuhan Xinxinjiali Biotechnology Co., Ltd.;

[0177] Sodium bromide: S30442-500g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0178] Sodium hypochlorite: industrial grade, purity ≥99%, purchased from Wuhan Xinzhongke Chemical Technology Co., Ltd.;

[0179] Sodium hydroxide: industrial grade, purity ≥99%, purchased from Nanjing Chemical Reagent Co., Ltd.;

[0180] Octadecanamine: S30714-100g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0181] Hexagonal boron nitride: industrial grade, purity ≥99%, purchased from Zhejiang Yamei Nano Technology Co., Ltd.;

[0182] D-xylose: S11037-25g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0183] Metallocene polyethylene: 1018MA, purchased from Shanghai Pengyue New Materials Co., Ltd.;

[0184] Linear low-density polyethylene: 218WJ, purchased from Shanghai Pengyue New Materials Co., Ltd.;

[0185] Low-density polyethylene: M202, purchased from Dongguan Nabaichuan Plastic Chemical Co., Ltd.;

[0186] High-density polyethylene: 3000JE, purchased from Beijing New Plastic Century Trading Co., Ltd.;

[0187] Maleic anhydride grafted ethylene-octene copolymer: CMG5805, purchased from Jiayirong Compatibilizer Jiangsu Co., Ltd.;

[0188] Maleic anhydride grafted polyethylene: T25141-100g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0189] Ultraviolet absorber UV-531: purity ≥98%, purchased from Hubei Rishengchang New Material Technology Co., Ltd.;

[0190] Ultraviolet absorber UV-326: S65102-25g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0191] Ultraviolet absorber UV-234: GA2224, purchased from Hubei Guangao Biotechnology Co., Ltd.;

[0192] Antioxidant 1010: S67391-25g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0193] Antioxidant 1076: purity ≥99%, purchased from Tianmen Hengchang Chemical Co., Ltd.;

[0194] Antioxidant 626: S99546-25g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0195] Antioxidant 168: S31114-100g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0196] Liquid paraffin: S68179-100ml, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0197] Silicone oil: S49332-250ml, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0198] Ethylene glycol: B25695-5ml, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0199] Stearic acid: S30473-500g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0200] Zinc stearate: S24319-500g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0201] Calcium stearate: S24307-250g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0202] Glycerol: purity ≥99.5%, purchased from Shandong Yonglida New Materials Technology Co., Ltd.;

[0203] Epoxidized soybean oil: S50881-100ml, purchased from Shanghai Yuanye Biotechnology Co., Ltd.;

[0204] Paraffin oil: purity ≥99%, purchased from Hubei Wonder Chemical Co., Ltd.

[0205] Example 1

[0206] This embodiment provides a method for preparing a high barrier and puncture-resistant polyethylene composite film. Figure 1 As shown, the preparation method specifically comprises the following steps:

[0207] (1) Dispersing montmorillonite in deionized water, ultrasonically dispersing to obtain a montmorillonite dispersion with a mass fraction of 5 wt%, and dropping a 0.05 mol / L hydrochloric acid solution into the montmorillonite dispersion to adjust its pH value to 7; dissolving hexadecyltrimethylammonium bromide in deionized water to obtain a modified solution with a concentration of 0.4 g / mL, and dropping the modified solution into the montmorillonite dispersion under 70°C water bath heating and mechanical stirring conditions for hydrothermal reaction, wherein the mass ratio of hexadecyltrimethylammonium bromide to montmorillonite is 1:3. After all the addition is completed, stirring is continued for 1.5 h, and then the organic montmorillonite is obtained after filtration, washing and drying;

[0208] The silane coupling agent KH550 and the ethanol aqueous solution are uniformly mixed and allowed to stand to obtain a coupling agent solution with a mass fraction of 5wt%, wherein the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 8:2; then a hydrochloric acid solution with a concentration of 0.05mol / L is added dropwise to the coupling agent solution to adjust its pH value to 5; the organic montmorillonite is dispersed in the coupling agent solution, and the mass ratio of the organic montmorillonite to the silane coupling agent KH550 in the coupling agent solution is 1:0.5, and then ultrasonically dispersed at 80°C for 3h, and finally filtered, washed, dried, ground and passed through a 200-mesh sieve to obtain modified montmorillonite;

[0209] (2) Dispersing cellulose in N,N-dimethylacetamide at a ratio of 0.01 g:1 mL, stirring and heating at 140°C for 3 h to obtain a cellulose dispersion, adding anhydrous lithium chloride to the cellulose dispersion at a ratio of 1 mL:0.06 g, stirring and heating at 80°C for 2 h, filtering and washing, and freeze-drying at -40°C for 24 h after washing to obtain pretreated cellulose;

[0210] Pretreated cellulose was dispersed in deionized water to obtain a cellulose suspension with a concentration of 0.01 g / mL, TEMPO and sodium bromide were added to the cellulose suspension, the mass ratio of pretreated cellulose, TEMPO and sodium bromide was 1:0.06:0.2, and the mixture was uniformly mixed to obtain a precursor solution, a sodium hypochlorite solution with a concentration of 0.3 g / mL was added dropwise to the precursor solution to cause an oxidation reaction, the mass ratio of the pretreated cellulose to the sodium hypochlorite was 1:5, and during the oxidation reaction, an alkali solution with a concentration of 0.1 mol / L was added dropwise to the precursor solution to control its pH value at 10, and a product solution was obtained after the oxidation reaction for 4 hours, and after the reaction was completed, the product solution was subjected to high-pressure homogenization at 70 MPa for 8 times to obtain a nanocellulose solution with a mass fraction of 0.5 wt%;

[0211] Dissolving octadecylamine in an ethanol aqueous solution to obtain an octadecylamine solution with a mass fraction of 2 g / L, wherein the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 7:3, mixing the nanocellulose solution with the octadecylamine solution, wherein the mass ratio of pure dry nanocellulose in the nanocellulose solution to octadecylamine in the octadecylamine solution is 3:1, then stirring and heating at 55° C. for 5 h to cause an amidation reaction, finally centrifuging and washing, and after washing, freeze-drying at -40° C. for 24 h to obtain modified nanocellulose;

[0212] (3) Heating the hexagonal boron nitride to 800°C at a heating rate of 10°C / min and keeping the temperature for 40 minutes to complete the calcination treatment to obtain calcined boron nitride, dispersing the calcined boron nitride in deionized water to form a boron nitride dispersion, and the ratio of calcined boron nitride to deionized water is 1g:100mL; then, ultrasonically stripping the boron nitride dispersion at an ultrasonic power of 200W for 2 hours, and finally filtering, washing and drying to obtain hydroxylated boron nitride;

[0213] The hydroxylated boron nitride and D-xylose were mixed and ball-milled in a mass ratio of 1:0.15 to obtain a composite powder, the ball milling speed was 150r / min, and the ball milling time was 12h; then, the composite powder was dispersed in deionized water to form a powder dispersion with a mass fraction of 0.5wt%, the powder dispersion was centrifuged, and the precipitate was dried to obtain xylose-modified boron nitride; the xylose-modified boron nitride was immersed in a silane coupling agent KH550 solution with a mass fraction of 5wt% at a temperature of 50°C for 5h (the solvent in the silane coupling agent KH550 solution was an ethanol aqueous solution, and the volume ratio of ethanol to deionized water was 8:2), and then filtered, washed and dried to obtain modified boron nitride;

[0214] (4) 50 parts by weight of metallocene polyethylene, 25 parts by weight of linear low-density polyethylene, 18 parts by weight of low-density polyethylene, 4 parts by weight of glycerol, 1.5 parts by weight of antioxidant 1010, 1.2 parts by weight of stearic acid and 0.3 parts by weight of ultraviolet absorber UV-531 were mixed uniformly to obtain a substrate layer raw material;

[0215] 70 parts by weight of high-density polyethylene, 15 parts by weight of modified montmorillonite, 6 parts by weight of modified nanocellulose, 5 parts by weight of glycerol, 3 parts by weight of liquid paraffin and 1 part by weight of stearic acid were uniformly mixed to obtain a barrier layer raw material;

[0216] 75 parts by weight of high-density polyethylene, 6 parts by weight of maleic anhydride grafted ethylene-octene copolymer, 3 parts by weight of maleic anhydride grafted polyethylene, 5 parts by weight of modified boron nitride, 5 parts by weight of glycerol, 3 parts by weight of liquid paraffin and 1 part by weight of stearic acid are uniformly mixed to obtain a puncture-resistant layer raw material, wherein the maleic anhydride grafting rate of the maleic anhydride grafted polyethylene is 5%, and the maleic anhydride grafting rate of the maleic anhydride grafted ethylene-octene copolymer is 10%;

[0217] The substrate layer raw material, the barrier layer raw material and the puncture-resistant layer raw material are fed into a three-layer co-extrusion film blowing machine in a mass ratio of 1:1.5:2.5, wherein the temperature of the first zone of the three-layer co-extrusion film blowing machine is 160°C, the temperature of the second zone is 165°C, the temperature of the third zone is 170°C, the temperature of the fourth zone is 180°C, and the temperature of the fifth zone is 175°C; the three-layer die is combined and extruded, and a composite cast sheet is obtained after rapid cooling, and the composite cast sheet is sequentially stretched transversely and longitudinally, wherein the temperature of the transverse stretching is 120°C, and the stretching ratio of the transverse stretching is 7, and the temperature of the longitudinal stretching is 110°C, and the stretching ratio of the longitudinal stretching is 4; after stretching, it is pulled to a winding device, and the high barrier and puncture-resistant polyethylene composite film is obtained after corona treatment and winding.

[0218] The high barrier and puncture-resistant polyethylene composite film is composed of a substrate layer, a barrier layer and an anti-puncture layer stacked in sequence, wherein the thickness of the substrate layer is 10 μm, the thickness of the barrier layer is 20 μm, and the thickness of the anti-puncture layer is 30 μm.

[0219] Figure 2 The XRD diagrams of the unmodified montmorillonite and the modified montmorillonite prepared in this embodiment after combined modification with hexadecyltrimethylammonium bromide and silane coupling agent are shown in the figure. It can be seen from the figure that the 2θ of the d001 crystal plane diffraction peak of the unmodified montmorillonite is 5.70°, and its average interlayer spacing is 1.54nm after calculation; the 2θ of the d001 crystal plane diffraction peak of the modified montmorillonite after combined modification with hexadecyltrimethylammonium bromide and silane coupling agent is 2.33°, and its average interlayer spacing is 3.78nm after calculation. It can be seen that the interlayer spacing of the modified montmorillonite after combined modification with hexadecyltrimethylammonium bromide and silane coupling agent has been significantly improved.

[0220] Figure 3 and Figure 4 The scanning electron microscope images of the nanocellulose solution prepared in this example at different magnifications are shown. It can be seen from the images that the nanocellulose is a filamentous structure with a high aspect ratio and a clear and smooth surface.

[0221] Figure 5 and Figure 6The figures are scanning electron microscope images of the modified nanocellulose prepared in this embodiment at different magnifications. It can be seen from the figures that the surface of the modified nanocellulose obtained by amidation modification of nanocellulose and octadecylamine shows obvious micro / nano rough structure, which is one of the important reasons why the modified nanocellulose has good hydrophobicity. At the same time, octadecylamine is also a low surface energy substance. The octadecylamine molecular chains are grafted onto the nanocellulose through the amidation reaction, which greatly reduces the surface energy of the nanocellulose. The present invention achieves the improvement of the hydrophobicity of the modified nanocellulose by constructing a good rough structure and a low surface energy surface.

[0222] Figure 7 The infrared spectra of octadecylamine, the nanocellulose solution prepared in this embodiment without octadecylamine amidation modification, and the modified nanocellulose after octadecylamine amidation modification are compared. The infrared spectra of the nanocellulose without octadecylamine amidation modification and the modified nanocellulose after octadecylamine amidation modification are shown in Figure 1467cm -1 and 1607cm -1 New absorption peaks appeared near 2916 cm-1, which were attributed to the NH and CN stretching vibrations of octadecylamine. In addition, the infrared spectrum of modified nanocellulose after amidation with octadecylamine showed a peak at 2916 cm-1. -1 and 2848cm -1 The sharp absorption peak at , which matches the CH stretching vibration of CH2 in octadecylamine. Therefore, it can be considered that octadecylamine is successfully grafted onto the modified nanocellulose prepared in this example.

[0223] Figure 8 and Fig. 9 The scanning electron microscope images of the hydroxylated boron nitride and xylose-modified boron nitride prepared in this embodiment are shown respectively. It can be seen from the figure that the hydroxylated boron nitride is a flaky structure with an average diameter of about 30 μm and a thickness of about 1.3 μm; the size of the xylose-modified boron nitride obtained after the auxiliary ball milling and exfoliation of D-xylose is significantly reduced, and is broken into small and thin fragments with a size of several microns. This is because D-xylose with a tiny crystal structure can enhance the friction and pressure between the hydroxylated boron nitride during the ball milling process, thereby promoting the exfoliation and stratification of the hydroxylated boron nitride.

[0224] Example 2

[0225] This embodiment provides a method for preparing a high barrier and puncture-resistant polyethylene composite film. Figure 1 As shown, the preparation method specifically comprises the following steps:

[0226] (1) Dispersing montmorillonite in deionized water, ultrasonically dispersing to obtain a montmorillonite dispersion with a mass fraction of 6 wt%, and dropping a hydrochloric acid solution with a concentration of 0.08 mol / L into the montmorillonite dispersion to adjust its pH value to 6.8; dissolving hexadecyltrimethylammonium bromide in deionized water to obtain a modified solution with a concentration of 0.42 g / mL, and dropping the modified solution into the montmorillonite dispersion under 72°C water bath heating and mechanical stirring conditions for hydrothermal reaction, wherein the mass ratio of hexadecyltrimethylammonium bromide to montmorillonite is 1:3.2. After all the addition is completed, stirring is continued for 1.8 h, and then the organic montmorillonite is obtained after filtration, washing and drying;

[0227] The silane coupling agent KH550 and the ethanol aqueous solution are uniformly mixed and allowed to stand to obtain a coupling agent solution with a mass fraction of 6wt%, wherein the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 8.2:1.8; then a hydrochloric acid solution with a concentration of 0.08mol / L is added dropwise to the coupling agent solution to adjust its pH value to 4.8; the organic montmorillonite is dispersed in the coupling agent solution, and the mass ratio of the organic montmorillonite to the silane coupling agent KH550 in the coupling agent solution is 1:0.48, and then ultrasonically dispersed at 82°C for 2.8h, and finally filtered, washed, dried, ground and passed through a 220-mesh sieve to obtain modified montmorillonite;

[0228] (2) Dispersing cellulose in N,N-dimethylacetamide at a ratio of 0.015 g:1 mL of cellulose and heating at 142°C for 2.8 h to obtain a cellulose dispersion, adding anhydrous lithium chloride to the cellulose dispersion at a ratio of 1 mL:0.065 g of N,N-dimethylacetamide and heating at 85°C for 1.8 h, filtering and washing, and freeze-drying at -42°C for 22 h after washing to obtain pretreated cellulose;

[0229] Pretreated cellulose was dispersed in deionized water to obtain a cellulose suspension with a concentration of 0.0105 g / mL, TEMPO and sodium bromide were added to the cellulose suspension, the mass ratio of pretreated cellulose, TEMPO and sodium bromide was 1:0.065:0.22, and the mixture was uniformly mixed to obtain a precursor solution, a sodium hypochlorite solution with a concentration of 0.35 g / mL was added dropwise to the precursor solution to cause an oxidation reaction, the mass ratio of the pretreated cellulose to the sodium hypochlorite was 1:6, and during the oxidation reaction, an alkali solution with a concentration of 0.1 mol / L was added dropwise to the precursor solution to control its pH value at 10.2, and a product solution was obtained after the oxidation reaction for 4.2 hours, and after the reaction was completed, the product solution was subjected to high-pressure homogenization at 72 MPa for 7 times to obtain a nanocellulose solution with a mass fraction of 0.8 wt%;

[0230] Dissolving octadecylamine in an ethanol aqueous solution to obtain an octadecylamine solution with a mass fraction of 2.5 g / L, wherein the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 7.5:2.5, mixing the nanocellulose solution with the octadecylamine solution, wherein the mass ratio of pure dry nanocellulose in the nanocellulose solution to octadecylamine in the octadecylamine solution is 2.8:1, then stirring and heating at 58° C. for 4.5 h to cause an amidation reaction, finally centrifuging and washing, and after washing, freeze-drying at -42° C. for 22 h to obtain modified nanocellulose;

[0231] (3) Heating the hexagonal boron nitride to 820°C at a heating rate of 12°C / min and keeping the temperature for 38 minutes to complete the calcination treatment to obtain calcined boron nitride, dispersing the calcined boron nitride in deionized water to form a boron nitride dispersion, and the ratio of calcined boron nitride to deionized water is 1g:105mL; then, ultrasonic stripping the boron nitride dispersion at an ultrasonic power of 220W for 1.8h, and finally filtering, washing and drying to obtain hydroxylated boron nitride;

[0232] The hydroxylated boron nitride and D-xylose were mixed and ball-milled in a mass ratio of 1:0.18 to obtain a composite powder, the ball milling speed was 180r / min, and the ball milling time was 11.5h; then, the composite powder was dispersed in deionized water to form a powder dispersion with a mass fraction of 0.8wt%, the powder dispersion was centrifuged, and the precipitate was dried to obtain xylose-modified boron nitride; the xylose-modified boron nitride was immersed in a silane coupling agent KH550 solution with a mass fraction of 5.2wt% at a temperature of 52°C for 4.5h (the solvent in the silane coupling agent KH550 solution was an ethanol aqueous solution, and the volume ratio of ethanol to deionized water was 8.2:1.8), and then filtered, washed and dried to obtain modified boron nitride;

[0233] (4) 52 parts by weight of metallocene polyethylene, 22 parts by weight of linear low-density polyethylene, 20 parts by weight of low-density polyethylene, 3 parts by weight of glycerol, 1.5 parts by weight of antioxidant 1076, 0.8 parts by weight of stearic acid and 0.7 parts by weight of ultraviolet absorber UV-531 were mixed to obtain a substrate layer raw material;

[0234] 72 parts by weight of high-density polyethylene, 15 parts by weight of modified montmorillonite, 6 parts by weight of modified nanocellulose, 5 parts by weight of glycerol, 1 part by weight of liquid paraffin and 1 part by weight of stearic acid were uniformly mixed to obtain a barrier layer raw material;

[0235] 78 parts by weight of high-density polyethylene, 5 parts by weight of maleic anhydride grafted ethylene-octene copolymer, 4 parts by weight of maleic anhydride grafted polyethylene, 5 parts by weight of modified boron nitride, 5 parts by weight of glycerol, 1.8 parts by weight of liquid paraffin and 1.2 parts by weight of stearic acid are uniformly mixed to obtain a raw material for an anti-puncture layer, wherein the maleic anhydride grafting rate of the maleic anhydride grafted polyethylene is 6%, and the maleic anhydride grafting rate of the maleic anhydride grafted ethylene-octene copolymer is 11%;

[0236] The substrate layer raw material, the barrier layer raw material and the puncture-resistant layer raw material are fed into a three-layer co-extrusion film blowing machine in a mass ratio of 1:1.8:2, wherein the temperature of the first zone of the three-layer co-extrusion film blowing machine is 162°C, the temperature of the second zone is 168°C, the temperature of the third zone is 172°C, the temperature of the fourth zone is 182°C, and the temperature of the fifth zone is 178°C; the three-layer die is combined and extruded, and a composite cast sheet is obtained after rapid cooling, and the composite cast sheet is sequentially transversely stretched and longitudinally stretched, wherein the transverse stretching temperature is 122°C, and the transverse stretching ratio is 8, and the longitudinal stretching temperature is 112°C, and the longitudinal stretching ratio is 4.5; after stretching, it is pulled to a winding device, and the high barrier and puncture-resistant polyethylene composite film is obtained after corona treatment and winding.

[0237] The high barrier and puncture-resistant polyethylene composite film is composed of a substrate layer, a barrier layer and an anti-puncture layer stacked in sequence, wherein the thickness of the substrate layer is 12 μm, the thickness of the barrier layer is 22 μm, and the thickness of the anti-puncture layer is 28 μm.

[0238] Example 3

[0239] This embodiment provides a method for preparing a high barrier and puncture-resistant polyethylene composite film. Figure 1 As shown, the preparation method specifically comprises the following steps:

[0240] (1) Dispersing montmorillonite in deionized water, ultrasonically dispersing to obtain a montmorillonite dispersion with a mass fraction of 7 wt%, and dropping a 0.1 mol / L hydrochloric acid solution into the montmorillonite dispersion to adjust its pH value to 6.5; dissolving hexadecyltrimethylammonium bromide in deionized water to obtain a modified solution with a concentration of 0.45 g / mL, and dropping the modified solution into the montmorillonite dispersion under 75°C water bath heating and mechanical stirring conditions for hydrothermal reaction, wherein the mass ratio of hexadecyltrimethylammonium bromide to montmorillonite is 1:3.5. After all the addition is completed, stirring is continued for 2 h, and then filtering, washing and drying to obtain an organic montmorillonite;

[0241] The silane coupling agent KH560 and the ethanol aqueous solution are uniformly mixed and allowed to stand to obtain a coupling agent solution with a mass fraction of 7wt%, wherein the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 8.5:1.5; then a hydrochloric acid solution with a concentration of 0.1mol / L is added dropwise to the coupling agent solution to adjust its pH value to 4.5; the organic montmorillonite is dispersed in the coupling agent solution, and the mass ratio of the organic montmorillonite to the silane coupling agent KH560 in the coupling agent solution is 1:0.45, and then ultrasonically dispersed at 85°C for 2.5h, and finally filtered, washed, dried, ground and passed through a 250-mesh sieve to obtain modified montmorillonite;

[0242] (2) Dispersing cellulose in N,N-dimethylacetamide at a ratio of 0.02 g:1 mL, stirring and heating at 145°C for 2.5 h to obtain a cellulose dispersion, adding anhydrous lithium chloride to the cellulose dispersion at a ratio of 1 mL:0.07 g, stirring and heating at 90°C for 1.5 h, filtering and washing, and freeze-drying at -45°C for 20 h after washing to obtain pretreated cellulose;

[0243] Pretreated cellulose was dispersed in deionized water to obtain a cellulose suspension with a concentration of 0.011 g / mL, TEMPO and sodium bromide were added to the cellulose suspension, the mass ratio of pretreated cellulose, TEMPO and sodium bromide was 1:0.07:0.25, and the mixture was uniformly mixed to obtain a precursor solution, a sodium hypochlorite solution with a concentration of 0.4 g / mL was added dropwise to the precursor solution to cause an oxidation reaction, the mass ratio of pretreated cellulose to sodium hypochlorite was 1:7, and during the oxidation reaction, an alkali solution with a concentration of 0.1 mol / L was added dropwise to the precursor solution to control its pH value at 10.5, and a product solution was obtained after the oxidation reaction for 4.5 hours, and after the reaction was completed, the product solution was subjected to high-pressure homogenization at 75 MPa for 6 times to obtain a nanocellulose solution with a mass fraction of 1 wt%;

[0244] Dissolving octadecylamine in an ethanol aqueous solution to obtain an octadecylamine solution with a mass fraction of 3 g / L, wherein the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 8:2, mixing the nanocellulose solution with the octadecylamine solution, wherein the mass ratio of pure dry nanocellulose in the nanocellulose solution to octadecylamine in the octadecylamine solution is 2.5:1, then stirring and heating at 60° C. for 4 h to cause an amidation reaction, finally centrifuging and washing, and after washing, freeze-drying at -45° C. for 20 h to obtain modified nanocellulose;

[0245] (3) Heating the hexagonal boron nitride to 850°C at a heating rate of 15°C / min and keeping the temperature for 35 minutes to complete the calcination treatment to obtain calcined boron nitride, dispersing the calcined boron nitride in deionized water to form a boron nitride dispersion, and the ratio of calcined boron nitride to deionized water is 1g:110mL; then, ultrasonic stripping the boron nitride dispersion at an ultrasonic power of 250W for 1.5h, and finally filtering, washing and drying to obtain hydroxylated boron nitride;

[0246] The hydroxylated boron nitride and D-xylose were mixed and ball-milled in a mass ratio of 1:0.2 to obtain a composite powder, the ball milling speed was 200 r / min, and the ball milling time was 11 hours; then, the composite powder was dispersed in deionized water to form a powder dispersion with a mass fraction of 1wt%, the powder dispersion was centrifuged, and the precipitate was dried to obtain xylose-modified boron nitride; the xylose-modified boron nitride was immersed in a silane coupling agent KH560 solution with a mass fraction of 5.5wt% at a temperature of 55°C for 4 hours (the solvent in the silane coupling agent KH560 solution was an ethanol-water solution, and the volume ratio of ethanol to deionized water was 8.5:1.5), and then filtered, washed and dried to obtain modified boron nitride;

[0247] (4) 55 parts by weight of metallocene polyethylene, 20 parts by weight of linear low-density polyethylene, 17 parts by weight of low-density polyethylene, 5 parts by weight of epoxidized soybean oil, 1.2 parts by weight of antioxidant 1076, 1 part by weight of zinc stearate and 0.8 parts by weight of ultraviolet absorber UV-326 were mixed to obtain a substrate layer raw material;

[0248] 75 parts by weight of high-density polyethylene, 14 parts by weight of modified montmorillonite, 5 parts by weight of modified nanocellulose, 3 parts by weight of epoxidized soybean oil, 2 parts by weight of silicone oil and 1 part by weight of zinc stearate were uniformly mixed to obtain a barrier layer raw material;

[0249] 80 parts by weight of high-density polyethylene, 5 parts by weight of maleic anhydride grafted ethylene-octene copolymer, 3.5 parts by weight of maleic anhydride grafted polyethylene, 4 parts by weight of modified boron nitride, 4 parts by weight of epoxy soybean oil, 2.7 parts by weight of silicone oil and 0.8 parts by weight of zinc stearate are uniformly mixed to obtain a puncture-resistant layer raw material, wherein the maleic anhydride grafting rate of the maleic anhydride grafted polyethylene is 7%, and the maleic anhydride grafting rate of the maleic anhydride grafted ethylene-octene copolymer is 12%;

[0250] The substrate layer raw material, the barrier layer raw material and the puncture-resistant layer raw material are fed into a three-layer co-extrusion film blowing machine in a mass ratio of 1:2:2, wherein the temperature of the first zone of the three-layer co-extrusion film blowing machine is 165°C, the temperature of the second zone is 170°C, the temperature of the third zone is 175°C, the temperature of the fourth zone is 185°C, and the temperature of the fifth zone is 180°C; the three-layer die is combined and extruded, and a composite cast sheet is obtained after rapid cooling, and the composite cast sheet is sequentially transversely stretched and longitudinally stretched, wherein the transverse stretching temperature is 125°C, and the stretching ratio of the transverse stretching is 8, and the longitudinal stretching temperature is 115°C, and the stretching ratio of the longitudinal stretching is 5; after stretching, it is pulled to a winding device, and the high barrier and puncture-resistant polyethylene composite film is obtained after corona treatment and winding.

[0251] The high barrier and puncture-resistant polyethylene composite film is composed of a substrate layer, a barrier layer and an anti-puncture layer stacked in sequence, wherein the thickness of the substrate layer is 15 μm, the thickness of the barrier layer is 25 μm, and the thickness of the anti-puncture layer is 25 μm.

[0252] Example 4

[0253] This embodiment provides a method for preparing a high barrier and puncture-resistant polyethylene composite film. Figure 1 As shown, the preparation method specifically comprises the following steps:

[0254] (1) Dispersing montmorillonite in deionized water, ultrasonically dispersing to obtain a montmorillonite dispersion with a mass fraction of 8 wt%, and dropping a 0.12 mol / L hydrochloric acid solution into the montmorillonite dispersion to adjust its pH value to 6.2; dissolving hexadecyltrimethylammonium bromide in deionized water to obtain a modified solution with a concentration of 0.48 g / mL, and dropping the modified solution into the montmorillonite dispersion under 78°C water bath heating and mechanical stirring conditions for hydrothermal reaction, wherein the mass ratio of hexadecyltrimethylammonium bromide to montmorillonite is 1:3.8. After all the addition is completed, stirring is continued for 2.2 h, and then the organic montmorillonite is obtained after filtration, washing and drying;

[0255] The silane coupling agent KH570 and the ethanol aqueous solution are uniformly mixed and allowed to stand to obtain a coupling agent solution with a mass fraction of 8wt%, wherein the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 8.8:1.2; then a hydrochloric acid solution with a concentration of 0.12mol / L is added dropwise to the coupling agent solution to adjust its pH value to 4.2; the organic montmorillonite is dispersed in the coupling agent solution, and the mass ratio of the organic montmorillonite to the silane coupling agent KH570 in the coupling agent solution is 1:0.42, and then ultrasonically dispersed at 88°C for 2.2h, and finally filtered, washed, dried, ground and passed through a 280-mesh sieve to obtain modified montmorillonite;

[0256] (2) Dispersing cellulose in N,N-dimethylacetamide at a ratio of 0.025 g:1 mL of cellulose and heating at 148°C for 2.2 h to obtain a cellulose dispersion, adding anhydrous lithium chloride to the cellulose dispersion at a ratio of 1 mL:0.075 g of N,N-dimethylacetamide and heating at 95°C for 1.2 h, filtering and washing, and freeze-drying at -48°C for 15 h to obtain pretreated cellulose;

[0257] Pretreated cellulose was dispersed in deionized water to obtain a cellulose suspension with a concentration of 0.0115 g / mL, TEMPO and sodium bromide were added to the cellulose suspension, the mass ratio of pretreated cellulose, TEMPO and sodium bromide was 1:0.075:0.28, and the precursor solution was obtained after being evenly mixed, and a sodium hypochlorite solution with a concentration of 0.45 g / mL was added dropwise to the precursor solution to cause an oxidation reaction, and the mass ratio of the pretreated cellulose to the sodium hypochlorite was 1:7. During the oxidation reaction, an alkali solution with a concentration of 0.1 mol / L was added dropwise to the precursor solution to control its pH value at 10.8. After the oxidation reaction for 4.8 hours, a product solution was obtained, and after the reaction was completed, the product solution was subjected to high-pressure homogenization at 78 MPa for 5 times to obtain a nanocellulose solution with a mass fraction of 1.2 wt%;

[0258] Dissolving octadecylamine in an ethanol aqueous solution to obtain an octadecylamine solution with a mass fraction of 3.5 g / L, wherein the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 8.5:1.5, mixing the nanocellulose solution with the octadecylamine solution, wherein the mass ratio of pure dry nanocellulose in the nanocellulose solution to octadecylamine in the octadecylamine solution is 2.2:1, then stirring and heating at 62° C. for 3.5 h to cause an amidation reaction, finally centrifuging and washing, and after washing, freeze-drying at -48° C. for 15 h to obtain modified nanocellulose;

[0259] (3) Heating the hexagonal boron nitride to 880°C at a heating rate of 18°C / min and keeping the temperature for 32 minutes to complete the calcination treatment to obtain calcined boron nitride, dispersing the calcined boron nitride in deionized water to form a boron nitride dispersion, and the ratio of calcined boron nitride to deionized water is 1g:115mL; then, ultrasonic stripping the boron nitride dispersion at an ultrasonic power of 280W for 1.2h, and finally filtering, washing and drying to obtain hydroxylated boron nitride;

[0260] The hydroxylated boron nitride and D-xylose were mixed and ball-milled in a mass ratio of 1:0.22 to obtain a composite powder, the ball milling speed was 220 r / min, and the ball milling time was 10.5 h; then, the composite powder was dispersed in deionized water to form a powder dispersion with a mass fraction of 1.2 wt%, the powder dispersion was centrifuged, and the precipitate was dried to obtain xylose-modified boron nitride; the xylose-modified boron nitride was immersed in a silane coupling agent KH570 solution with a mass fraction of 5.8 wt% at a temperature of 58 ° C for 3.5 h (the solvent in the silane coupling agent KH570 solution was an ethanol aqueous solution, and the volume ratio of ethanol to deionized water was 8.8:1.2), and then filtered, washed and dried to obtain modified boron nitride;

[0261] (4) 58 parts by weight of metallocene polyethylene, 25 parts by weight of linear low-density polyethylene, 10 parts by weight of low-density polyethylene, 5 parts by weight of paraffin oil, 0.8 parts by weight of antioxidant 626, 0.8 parts by weight of calcium stearate and 0.4 parts by weight of ultraviolet absorber UV-326 were mixed to obtain a substrate layer raw material;

[0262] 78 parts by weight of high-density polyethylene, 13 parts by weight of modified montmorillonite, 4 parts by weight of modified nanocellulose, 2 parts by weight of paraffin oil, 1.8 parts by weight of ethylene glycol and 1.2 parts by weight of calcium stearate were uniformly mixed to obtain a barrier layer raw material;

[0263] 82 parts by weight of high-density polyethylene, 5.5 parts by weight of maleic anhydride grafted ethylene-octene copolymer, 3 parts by weight of maleic anhydride grafted polyethylene, 4 parts by weight of modified boron nitride, 5 parts by weight of paraffin oil, 1 part by weight of ethylene glycol and 1.2 parts by weight of calcium stearate are uniformly mixed to obtain a puncture-resistant layer raw material, wherein the maleic anhydride grafting rate of the maleic anhydride grafted polyethylene is 7%, and the maleic anhydride grafting rate of the maleic anhydride grafted ethylene-octene copolymer is 13%;

[0264] The substrate layer raw material, the barrier layer raw material and the puncture-resistant layer raw material are fed into a three-layer co-extrusion film blowing machine in a mass ratio of 1:2.2:1.5, wherein the temperature of the first zone of the three-layer co-extrusion film blowing machine is 168°C, the temperature of the second zone is 172°C, the temperature of the third zone is 178°C, the temperature of the fourth zone is 188°C, and the temperature of the fifth zone is 182°C; the three-layer die is combined and extruded, and a composite cast sheet is obtained after rapid cooling, and the composite cast sheet is sequentially transversely stretched and longitudinally stretched, wherein the transverse stretching temperature is 128°C, the transverse stretching ratio is 9, the longitudinal stretching temperature is 118°C, and the longitudinal stretching ratio is 5.5; after stretching, it is pulled to a winding device, and the high barrier and puncture-resistant polyethylene composite film is obtained after corona treatment and winding.

[0265] The high barrier and puncture-resistant polyethylene composite film is composed of a substrate layer, a barrier layer and an anti-puncture layer stacked in sequence, wherein the thickness of the substrate layer is 18 μm, the thickness of the barrier layer is 28 μm, and the thickness of the anti-puncture layer is 20 μm.

[0266] Example 5

[0267] This embodiment provides a method for preparing a high barrier and puncture-resistant polyethylene composite film. Figure 1 As shown, the preparation method specifically comprises the following steps:

[0268] (1) Dispersing montmorillonite in deionized water, ultrasonically dispersing to obtain a montmorillonite dispersion with a mass fraction of 10 wt%, and dropping a 0.15 mol / L hydrochloric acid solution into the montmorillonite dispersion to adjust its pH value to 6; dissolving hexadecyltrimethylammonium bromide in deionized water to obtain a modified solution with a concentration of 0.5 g / mL, and dropping the modified solution into the montmorillonite dispersion under 80°C water bath heating and mechanical stirring conditions for hydrothermal reaction, wherein the mass ratio of hexadecyltrimethylammonium bromide to montmorillonite is 1:4. After all the addition is completed, stirring is continued for 2.5 h, and then filtering, washing and drying to obtain an organic montmorillonite;

[0269] The silane coupling agent KH570 and the ethanol aqueous solution are uniformly mixed and allowed to stand to obtain a coupling agent solution with a mass fraction of 10wt%, wherein the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 9:1; then a hydrochloric acid solution with a concentration of 0.15mol / L is added dropwise to the coupling agent solution to adjust its pH value to 4; organic montmorillonite is dispersed in the coupling agent solution, and the mass ratio of the organic montmorillonite to the silane coupling agent KH570 in the coupling agent solution is 1:0.4, and then ultrasonically dispersed at 90°C for 2h, and finally filtered, washed, dried, ground and passed through a 300-mesh sieve to obtain modified montmorillonite;

[0270] (2) Dispersing cellulose in N,N-dimethylacetamide at a ratio of 0.03 g:1 mL of cellulose and heating at 150°C for 2 h to obtain a cellulose dispersion, adding anhydrous lithium chloride to the cellulose dispersion at a ratio of 1 mL:0.08 g of N,N-dimethylacetamide and heating at 100°C for 1 h, filtering and washing, and freeze-drying at -50°C for 12 h to obtain pretreated cellulose;

[0271] Pretreated cellulose was dispersed in deionized water to obtain a cellulose suspension with a concentration of 0.012 g / mL, TEMPO and sodium bromide were added to the cellulose suspension, the mass ratio of pretreated cellulose, TEMPO and sodium bromide was 1:0.08:0.3, and the mixture was uniformly mixed to obtain a precursor solution, a sodium hypochlorite solution with a concentration of 0.5 g / mL was added dropwise to the precursor solution to cause an oxidation reaction, the mass ratio of pretreated cellulose to sodium hypochlorite was 1:8, and during the oxidation reaction, an alkali solution with a concentration of 0.1 mol / L was added dropwise to the precursor solution to control its pH value at 11, and a product solution was obtained after the oxidation reaction for 5 hours, and after the reaction was completed, the product solution was subjected to high-pressure homogenization at 80 MPa for 5 times to obtain a nanocellulose solution with a mass fraction of 1.5 wt%;

[0272] Dissolving octadecylamine in an ethanol aqueous solution to obtain an octadecylamine solution with a mass fraction of 4 g / L, wherein the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 9:1, mixing the nanocellulose solution with the octadecylamine solution, wherein the mass ratio of pure dry nanocellulose in the nanocellulose solution to octadecylamine in the octadecylamine solution is 2:1, then stirring and heating at 65° C. for 3 h to cause an amidation reaction, finally centrifuging and washing, and after washing, freeze-drying at -50° C. for 12 h to obtain modified nanocellulose;

[0273] (3) Heating the hexagonal boron nitride to 900°C at a heating rate of 20°C / min and keeping the temperature for 30 minutes to complete the calcination treatment to obtain calcined boron nitride, dispersing the calcined boron nitride in deionized water to form a boron nitride dispersion, and the ratio of calcined boron nitride to deionized water is 1g:120mL; then, ultrasonically stripping the boron nitride dispersion at an ultrasonic power of 300W for 1h, and finally filtering, washing and drying to obtain hydroxylated boron nitride;

[0274] The hydroxylated boron nitride and D-xylose were mixed and ball-milled in a mass ratio of 1:0.25 to obtain a composite powder, the ball milling speed was 250 r / min, and the ball milling time was 10 h; then, the composite powder was dispersed in deionized water to form a powder dispersion with a mass fraction of 1.5 wt%, the powder dispersion was centrifuged, and the precipitate was dried to obtain xylose-modified boron nitride; the xylose-modified boron nitride was immersed in a silane coupling agent KH570 solution with a mass fraction of 6 wt% at a temperature of 60 ° C for 3 h (the solvent in the silane coupling agent KH570 solution was an ethanol aqueous solution, and the volume ratio of ethanol to deionized water was 9:1), and then filtered, washed and dried to obtain modified boron nitride;

[0275] (4) 60 parts by weight of metallocene polyethylene, 15 parts by weight of linear low-density polyethylene, 18 parts by weight of low-density polyethylene, 5 parts by weight of paraffin oil, 0.5 parts by weight of antioxidant 168, 1 part by weight of calcium stearate and 0.5 parts by weight of ultraviolet absorber UV-234 were mixed uniformly to obtain a substrate layer raw material;

[0276] 80 parts by weight of high-density polyethylene, 12 parts by weight of modified montmorillonite, 4 parts by weight of modified nanocellulose, 2 parts by weight of paraffin oil, 1.2 parts by weight of ethylene glycol and 0.8 parts by weight of calcium stearate were uniformly mixed to obtain a barrier layer raw material;

[0277] 85 parts by weight of high-density polyethylene, 5 parts by weight of maleic anhydride grafted ethylene-octene copolymer, 3 parts by weight of maleic anhydride grafted polyethylene, 2 parts by weight of modified boron nitride, 2 parts by weight of paraffin oil, 2 parts by weight of ethylene glycol and 1 part by weight of calcium stearate are uniformly mixed to obtain a puncture-resistant layer raw material, wherein the maleic anhydride grafting rate of the maleic anhydride grafted polyethylene is 8%, and the maleic anhydride grafting rate of the maleic anhydride grafted ethylene-octene copolymer is 15%;

[0278] The substrate layer raw material, the barrier layer raw material and the puncture-resistant layer raw material are fed into a three-layer co-extrusion film blowing machine in a mass ratio of 1:2.5:2.5, wherein the temperature of the first zone of the three-layer co-extrusion film blowing machine is 170°C, the temperature of the second zone is 175°C, the temperature of the third zone is 180°C, the temperature of the fourth zone is 190°C, and the temperature of the fifth zone is 185°C; the three-layer die is combined and extruded, and a composite cast sheet is obtained after rapid cooling, and the composite cast sheet is sequentially transversely stretched and longitudinally stretched, wherein the transverse stretching temperature is 130°C, the transverse stretching ratio is 10, the longitudinal stretching temperature is 120°C, and the longitudinal stretching ratio is 6; after stretching, it is pulled to a winding device, and the high barrier and puncture-resistant polyethylene composite film is obtained after corona treatment and winding.

[0279] The high barrier and puncture-resistant polyethylene composite film is composed of a substrate layer, a barrier layer and an anti-puncture layer stacked in sequence, wherein the thickness of the substrate layer is 20 μm, the thickness of the barrier layer is 30 μm, and the thickness of the anti-puncture layer is 30 μm.

[0280] Comparative Example 1

[0281] This comparative example provides a method for preparing a high barrier and puncture-resistant polyethylene composite film, which differs from Example 1 in that, in step (2), the mass ratio of pure dry nanocellulose in the nanocellulose solution to octadecylamine in the octadecylamine solution is adjusted to 1.5:1, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0282] Comparative Example 2

[0283] This comparative example provides a method for preparing a high barrier and puncture-resistant polyethylene composite film, which differs from Example 1 in that, in step (2), the mass ratio of pure dry nanocellulose in the nanocellulose solution to octadecylamine in the octadecylamine solution is adjusted to 3.5:1, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0284] Comparative Example 3

[0285] This comparative example provides a method for preparing a high barrier and puncture-resistant polyethylene composite film. The difference from Example 1 is that in step (4), the weight portion of the modified nanocellulose in the barrier layer is adjusted to 3 parts, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0286] Comparative Example 4

[0287] This comparative example provides a method for preparing a high barrier and puncture-resistant polyethylene composite film. The difference from Example 1 is that in step (4), the weight portion of the modified nanocellulose in the barrier layer is adjusted to 7 parts, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0288] Comparative Example 5

[0289] This comparative example provides a method for preparing a high barrier and puncture-resistant polyethylene composite film. The difference from Example 1 is that in step (4), the weight portion of the maleic anhydride grafted ethylene-octene copolymer in the puncture-resistant layer is adjusted to 4 parts, and the other process parameters and operation steps are exactly the same as those in Example 1.

[0290] Comparative Example 6

[0291] This comparative example provides a method for preparing a high barrier and puncture-resistant polyethylene composite film. The difference from Example 1 is that in step (4), the weight portion of the maleic anhydride grafted ethylene-octene copolymer in the puncture-resistant layer is adjusted to 7 parts, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0292] Comparative Example 7

[0293] This comparative example provides a method for preparing a high barrier and puncture-resistant polyethylene composite film. The difference from Example 1 is that in step (4), the weight portion of the modified boron nitride in the puncture-resistant layer is adjusted to 1 part, and the other process parameters and operation steps are exactly the same as those in Example 1.

[0294] Comparative Example 8

[0295] This comparative example provides a method for preparing a high barrier and puncture-resistant polyethylene composite film. The difference from Example 1 is that in step (4), the weight portion of the modified boron nitride in the puncture-resistant layer is adjusted to 6 parts, and the other process parameters and operation steps are exactly the same as those in Example 1.

[0296] Fig.10 and Fig.11 The scanning electron microscope images of the tensile cross-section of the puncture-resistant layer prepared in Example 1 and Comparative Example 8 are shown in FIG. Fig.10 (Example 1) It can be seen that the modified boron nitride is evenly dispersed in the polymer matrix without obvious agglomeration. After stretching, the high-density polyethylene continuous phase in the puncture-resistant layer is stretched and deformed, and the modified boron nitride is evenly embedded in the polymer matrix, forming a network structure composed of matrix fiber filaments and cavities. Fig.11 In (Comparative Example 8), boron nitride agglomerates (as indicated by the arrows) formed by the agglomeration of modified boron nitride can be clearly seen. This is because the modified boron nitride in Comparative Example 8 is added in excess, and the non-covalent interaction between the modified boron nitride layers is strong. When the content in the anti-puncture layer is high, the dispersibility becomes poor and agglomeration is easy to occur. These boron nitride agglomerates will cause defects inside the anti-puncture layer, thereby causing the elongation at break of the polyethylene composite film to decrease.

[0297] The mechanical properties, puncture resistance and barrier properties of the high barrier and puncture resistant polyethylene composite films provided in Examples 1-5 and Comparative Examples 1-8 were tested, and the specific test steps are as follows:

[0298] (1) Mechanical properties test

[0299] The high barrier and puncture-resistant polyethylene composite films provided in Examples 1-5 and Comparative Examples 1-8 were cut into rectangular strip specimens of 1.5 cm × 10 cm, and the specimens were stretched using a universal material testing machine until they broke. The initial distance between the clamps was 75 mm, and the stretching speed was 50 mm / min. The tensile strength and elongation at break were calculated. Five specimens were prepared for each group of Examples and Comparative Examples, and the results were averaged.

[0300] (2) Puncture resistance test

[0301] The puncture resistance of the high barrier and puncture resistant polyethylene composite films provided in Examples 1-5 and Comparative Examples 1-8 was tested with reference to GB / T17643-2011 "Geosynthetic Polyethylene Geomembrane". The polyethylene composite film was fixed with a ring fixture having an inner diameter of 45±0.025mm so that it could not slide. A metal rod was inserted into the polyethylene composite film at a test no-load speed of 300±10mm / min until the metal rod completely pierced the polyethylene composite film. The maximum force value was recorded as the puncture resistance. Five specimens were prepared for each group of Examples and Comparative Examples, and the results were averaged.

[0302] (3) Barrier performance test

[0303] The high barrier and puncture-resistant polyethylene composite films provided in Examples 1-5 and Comparative Examples 1-8 were cut into samples of 120 mm×60 mm×0.2 mm, which were folded in half and heat-sealed on both sides with a sealing machine to form a plastic film bag of 60 mm×60 mm×0.2 mm. 5 mL of deionized water was added to the plastic film bag, and the bag was heat-sealed and weighed to record the initial weight. The plastic film bag containing deionized water was placed in a blast oven at 50°C for 12 hours, and then placed at room temperature for 12 hours. This was a one-day test process. The test process was the same every day until the weight of the plastic film bag containing deionized water was weighed again after the 35th day. The barrier properties of the polyethylene composite film were reflected by the weight loss rate (water permeability). Five samples were prepared for each group of Examples and Comparative Examples, and the results were averaged.

[0304] The test results are shown in Table 1.

[0305] Table 1 Test results of high barrier and puncture resistant polyethylene composite films provided by Examples 1-5 and Comparative Examples 1-8

[0306]

[0307] It can be seen from the test data provided in Table 1 that the tensile strength and elongation at break of the high barrier puncture resistant polyethylene composite film prepared in Examples 1-5 are higher than those in Comparative Examples 1-8, which indicates that the high barrier puncture resistant polyethylene composite film prepared by the preparation method provided by the present invention has excellent mechanical properties. Secondly, the puncture resistance of the high barrier puncture resistant polyethylene composite film prepared in Examples 1-5 is higher than that in Comparative Examples 1-8, which indicates that the high barrier puncture resistant polyethylene composite film prepared by the preparation method provided by the present invention has excellent puncture resistance. Thirdly, the water permeability of the high barrier puncture resistant polyethylene composite film prepared in Examples 1-5 is lower than that in Comparative Examples 1-8, which indicates that the high barrier puncture resistant polyethylene composite film prepared by the preparation method provided by the present invention has excellent barrier properties.

[0308] It can be seen from the test data of Example 1, Comparative Example 1 and Comparative Example 2 that the tensile strength and elongation at break of the high barrier puncture resistant polyethylene composite film prepared in Comparative Example 1 and Comparative Example 2 are lower than those in Example 1, while the water permeability is higher than that in Example 1. This indicates that the mechanical properties and barrier properties of the high barrier puncture resistant polyethylene composite film prepared in Comparative Example 1 and Comparative Example 2 are lower than those in Example 1. This is because the amount of octadecylamine used in Comparative Example 1 is relatively high, and too many long chains of octadecylamine molecules are entangled with -NH2 as the core, which hinders the occurrence of the amidation reaction, resulting in a decrease in the hydrophobicity of the modified nanocellulose, thereby affecting the interfacial compatibility between the modified nanocellulose and the polymer matrix, so that the mechanical properties and barrier properties of the polyethylene composite film finally prepared are affected to varying degrees. However, the amount of octadecylamine used in Comparative Example 2 is relatively low, resulting in a decrease in the amount of octadecylamine grafted on the nanocellulose, and the hydrophobicity of the modified nanocellulose cannot be effectively improved, which in turn affects the interfacial compatibility between the modified nanocellulose and the polymer matrix, so that the mechanical properties and barrier properties of the finally prepared polyethylene composite film are affected to varying degrees.

[0309] It can be seen from the test data of Example 1, Comparative Example 3 and Comparative Example 4 that the tensile strength and elongation at break of the high barrier puncture-resistant polyethylene composite film prepared in Comparative Example 3 and Comparative Example 4 are lower than those in Example 1, while the water permeability is higher than that in Example 1, which indicates that the mechanical properties and barrier properties of the high barrier puncture-resistant polyethylene composite film prepared in Comparative Example 3 and Comparative Example 4 are lower than those in Example 1. This is because the amount of modified nanocellulose added in Comparative Example 3 is too low, and the mechanical reinforcement and moisture barrier effects of nanocellulose cannot be effectively exerted, resulting in a decrease in the mechanical properties and barrier properties of the polyethylene composite film finally prepared. The amount of modified nanocellulose added in Comparative Example 4 is too high, and the modified nanocellulose agglomerates in the polymer matrix, resulting in defects such as voids and holes inside the barrier layer, resulting in a decrease in the mechanical properties and barrier properties of the polyethylene composite film finally prepared.

[0310] It can be seen from the test data of Example 1, Comparative Example 5 and Comparative Example 6 that the tensile strength, elongation at break and puncture resistance of the high barrier puncture resistant polyethylene composite film prepared in Comparative Example 5 and Comparative Example 6 are all lower than those in Example 1, which indicates that the mechanical properties and puncture resistance of the high barrier puncture resistant polyethylene composite film prepared in Comparative Example 5 and Comparative Example 6 are lower than those in Example 1. This is because the addition amount of maleic anhydride grafted ethylene-octene copolymer in Comparative Example 5 is too low, and an effective flexible interface structure cannot be formed between the modified boron nitride and the polymer matrix, resulting in the puncture-resistant layer being prone to generate strong stress concentration at the interface between the modified boron nitride and the polymer matrix when subjected to a load, resulting in a decrease in the mechanical properties and puncture resistance of the polyethylene composite film finally prepared. In Comparative Example 6, the addition amount of maleic anhydride grafted ethylene-octene copolymer is too high. Since the ethylene-octene copolymer chain segment is a flexible chain with a lower modulus, when it is added in excess, it will also affect the mechanical properties and puncture resistance of the puncture-resistant layer to a certain extent.

[0311] It can be seen from the test data of Example 1, Comparative Example 7 and Comparative Example 8 that the tensile strength, elongation at break and puncture resistance of the high barrier puncture resistant polyethylene composite film prepared in Comparative Example 7 and Comparative Example 8 are lower than those in Example 1, while the water permeability is slightly higher than that in Example 1, which indicates that the mechanical properties, puncture resistance and barrier properties of the high barrier puncture resistant polyethylene composite film prepared in Comparative Example 7 and Comparative Example 8 are lower than those in Example 1. This is because the amount of modified boron nitride added in Comparative Example 7 is too low, so that the modified boron nitride cannot effectively exert its excellent mechanical enhancement effect, resulting in a decrease in the mechanical properties of the anti-puncture layer. At the same time, since the modified boron nitride has a high lateral size, the addition of the modified boron nitride can give the anti-puncture layer a certain barrier ability, while the amount of modified boron nitride added in Comparative Example 7 is too low, which affects the barrier properties of the anti-puncture layer. In Comparative Example 8, the amount of modified boron nitride added is too high, and it is easy to agglomerate inside the puncture-resistant layer to form agglomerates, resulting in weakened interfacial bonding between the modified boron nitride and the polymer matrix, which is easy to produce local stress concentration. At the same time, it also reduces the tortuosity of the water diffusion channel, ultimately affecting the mechanical properties, puncture resistance and barrier properties of the puncture-resistant layer.

[0312] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a high barrier and puncture-resistant polyethylene composite film, characterized in that: The preparation method comprises: The montmorillonite is modified with hexadecyltrimethylammonium bromide and silane coupling agent in sequence to obtain modified montmorillonite; Anhydrous lithium chloride is used to modify cellulose, and then a nanocellulose solution is prepared by TEMPO oxidation method, and finally the nanocellulose solution is amidated and modified by octadecylamine to obtain modified nanocellulose; The hexagonal boron nitride is subjected to calcination treatment, D-xylose modification and silane coupling agent modification in sequence to obtain modified boron nitride; The metallocene polyethylene, linear low-density polyethylene, low-density polyethylene, plasticizer, antioxidant, lubricant and ultraviolet absorber are uniformly mixed to obtain a substrate layer raw material; 70-80 parts by weight of high-density polyethylene, 12-15 parts by weight of the modified montmorillonite, 4-6 parts by weight of the modified nanocellulose, as well as a plasticizer, a dispersant and a lubricant are uniformly mixed to obtain a barrier layer raw material; 75-85 parts by weight of high-density polyethylene, 5-6 parts by weight of maleic anhydride grafted ethylene-octene copolymer, 3-4 parts by weight of maleic anhydride grafted polyethylene, 2-5 parts by weight of the modified boron nitride, as well as a plasticizer, a dispersant and a lubricant are uniformly mixed to obtain an anti-puncture layer raw material; The substrate layer raw material, the barrier layer raw material and the puncture-resistant layer raw material are fed into a three-layer co-extrusion film blowing machine, extruded through a three-layer die head, and rapidly cooled to obtain a composite cast sheet, and the composite cast sheet is sequentially stretched transversely and longitudinally, and after the stretching is completed, it is pulled to a winding device, and after corona treatment and winding, the high-barrier and puncture-resistant polyethylene composite film is obtained; The modified nanocellulose is prepared by the following method: The cellulose is dispersed in N,N-dimethylacetamide, stirred and heated to obtain a cellulose dispersion, anhydrous lithium chloride is added to the cellulose dispersion, stirred and heated to react, and then filtered, washed and freeze-dried for the first time to obtain pretreated cellulose; the pretreated cellulose is dispersed in deionized water to obtain a cellulose suspension, TEMPO and sodium bromide are added to the cellulose suspension, mixed evenly to obtain a precursor solution, sodium hypochlorite solution is added dropwise to the precursor solution to cause an oxidation reaction, a product solution is obtained after the reaction is completed, and the product solution is subjected to high-pressure homogenization to obtain a nanocellulose solution; the nanocellulose solution is mixed, stirred and heated with an octadecylamine solution to cause an amidation reaction, the mass ratio of pure dry nanocellulose in the nanocellulose solution to octadecylamine in the octadecylamine solution is (2-3):1, and then centrifuged, washed and freeze-dried for the second time to obtain modified nanocellulose.

2. The method for preparing a high barrier and puncture resistant polyethylene composite film according to claim 1, characterized in that: The modified montmorillonite is prepared by the following method: Dispersing montmorillonite in deionized water, obtaining a montmorillonite dispersion after ultrasonic dispersion, and dropping a hydrochloric acid solution into the montmorillonite dispersion to adjust its pH value; dissolving hexadecyltrimethylammonium bromide in deionized water to obtain a modified solution, and dropping the modified solution into the montmorillonite dispersion under water bath heating and mechanical stirring conditions to perform a hydrothermal reaction, continuing to stir after all the dropping is completed, and then filtering, washing and drying to obtain an organic montmorillonite; The silane coupling agent and the ethanol aqueous solution are uniformly mixed and allowed to stand to obtain a coupling agent solution, and a hydrochloric acid solution is added dropwise to the coupling agent solution to adjust the pH value thereof; the organic montmorillonite is dispersed in the coupling agent solution, ultrasonically dispersed and heated, and then filtered, washed, dried, ground and sieved to obtain the modified montmorillonite.

3. The method for preparing the high barrier and puncture resistant polyethylene composite film according to claim 2, characterized in that: The mass fraction of montmorillonite in the montmorillonite dispersion is 5-10wt%; The concentration of the hydrochloric acid solution is 0.05-0.15 mol / L; Adding hydrochloric acid solution dropwise to the montmorillonite dispersion to adjust the pH value to 6-7; The concentration of hexadecyltrimethylammonium bromide in the modified solution is 0.4-0.5 g / mL; The mass ratio of hexadecyltrimethylammonium bromide in the modified solution to the montmorillonite in the montmorillonite dispersion is 1:(3-4); The temperature of the hydrothermal reaction between the modified solution and the montmorillonite dispersion is 70-80° C.; After all the modified solution is dripped into the montmorillonite dispersion, stirring is continued for 1.5 to 2.5 hours; The mass fraction of the silane coupling agent in the coupling agent solution is 5-10wt%; The volume ratio of ethanol to deionized water in the ethanol aqueous solution is (8-9):(1-2); Adding hydrochloric acid solution dropwise to the coupling agent solution to adjust the pH value thereof to 4-5; The mass ratio of the organic montmorillonite to the silane coupling agent in the coupling agent solution is 1:(0.4-0.5); The heating temperature of the organic montmorillonite and the coupling agent solution during ultrasonic dispersion is 80-90° C.; The heating time of the organic montmorillonite and the coupling agent solution during ultrasonic dispersion is 2 to 3 hours; The mesh number of the sieve used for the sieving is 200-300 meshes.

4. The method for preparing a high barrier and puncture resistant polyethylene composite film according to claim 1, characterized in that: The ratio of cellulose to N,N-dimethylacetamide is (0.01-0.03) g:1 mL; The heating temperature when the cellulose and N,N-dimethylacetamide are mixed is 140-150°C; The stirring time when the cellulose and N,N-dimethylacetamide are mixed is 2 to 3 hours; The ratio of N,N-dimethylacetamide to anhydrous lithium chloride in the cellulose dispersion is 1 mL: (0.06-0.08) g; The heating temperature when the cellulose dispersion and anhydrous lithium chloride are mixed is 80-100°C; The stirring time when the cellulose dispersion and anhydrous lithium chloride are mixed is 1 to 2 hours; The first freeze-drying temperature is -40 to -50°C; The first freeze-drying time is 12 to 24 hours; The concentration of the pretreated cellulose in the cellulose suspension is 0.01-0.012 g / mL; The mass ratio of the pretreated cellulose, the TEMPO and the sodium bromide in the cellulose suspension is 1:(0.06-0.08):(0.2-0.3); The concentration of the sodium hypochlorite solution is 0.3-0.5 g / mL; The mass ratio of the pretreated cellulose in the precursor solution to the sodium hypochlorite in the sodium hypochlorite solution is 1:(5-8); During the oxidation reaction, an alkali solution with a concentration of 0.1 mol / L is added dropwise to the precursor solution to control the pH value thereof to be between 10 and 11; The oxidation reaction time is 4 to 5 hours; The pressure of the high pressure homogenization is 70-80 MPa; The number of times of high pressure homogenization is 5 to 8 times; The mass fraction of the nanocellulose solution is 0.5-1.5wt%; The octadecylamine solution is composed of octadecylamine and an ethanol aqueous solution, wherein the volume ratio of ethanol to deionized water in the ethanol aqueous solution is (7-9):(1-3); The mass fraction of octadecylamine in the octadecylamine solution is 2-4 g / L; The heating temperature when the nanocellulose solution and the octadecylamine solution are mixed is 55-65° C.; The stirring time when the nanocellulose solution and the octadecylamine solution are mixed is 3 to 5 hours; The second freeze drying temperature is -40 to -50°C; The second freeze-drying time is 12 to 24 hours.

5. The method for preparing a high barrier and puncture resistant polyethylene composite film according to claim 1, characterized in that: The modified boron nitride is prepared by the following method: The method comprises the steps of calcining hexagonal boron nitride to obtain calcined boron nitride, dispersing the calcined boron nitride in deionized water to form a boron nitride dispersion, ultrasonically exfoliating the boron nitride dispersion, filtering, washing and drying to obtain hydroxylated boron nitride; mixing the hydroxylated boron nitride with D-xylose and ball milling to obtain a composite powder, dispersing the composite powder in deionized water to form a powder dispersion, centrifuging the powder dispersion, and drying the precipitate to obtain xylose-modified boron nitride; The xylose-modified boron nitride is immersed in a silane coupling agent solution and heated, and then filtered, washed and dried to obtain the modified boron nitride.

6. The method for preparing a high barrier and puncture resistant polyethylene composite film according to claim 5, characterized in that: The calcination temperature of the hexagonal boron nitride is 800-900°C; The heating rate of the hexagonal boron nitride during calcination is 10-20°C / min; The holding time of the hexagonal boron nitride during calcination is 30 to 40 minutes; The ratio of the calcined boron nitride and deionized water when mixed is 1g: (100-120)mL; The ultrasonic power of the ultrasonic stripping of the boron nitride dispersion is 200-300W; The ultrasonic stripping time of the boron nitride dispersion is 1 to 2 hours; The mass ratio of the hydroxylated boron nitride to the D-xylose is 1:(0.15-0.25); The rotation speed of the mixed ball milling of the hydroxylated boron nitride and D-xylose is 150-250 r / min; The ball milling time of the hydroxylated boron nitride and D-xylose is 10-12 hours; The mass fraction of the composite powder in the powder dispersion is 0.5-1.5wt%; The silane coupling agent solution consists of a silane coupling agent and an ethanol aqueous solution; The mass fraction of the silane coupling agent in the silane coupling agent solution is 5-6wt%; The xylose-modified boron nitride is immersed in the silane coupling agent solution for 3 to 5 hours; The heating temperature when the xylose-modified boron nitride is immersed in the silane coupling agent solution is 50-60°C.

7. The method for preparing a high barrier and puncture resistant polyethylene composite film according to claim 6, characterized in that: The maleic anhydride grafted polyethylene has a maleic anhydride grafting rate of 5-8%; The maleic anhydride grafted ethylene-octene copolymer has a maleic anhydride grafting rate of 10 to 15%; The mass ratio of the substrate layer raw material, the barrier layer raw material and the puncture-resistant layer raw material is 1:(1.5-2.5):(1.5-2.5); The three-layer co-extrusion film blowing machine comprises three groups of single-screw extruders, and the raw materials of the substrate layer, the raw materials of the barrier layer and the raw materials of the anti-puncture layer are fed from different single-screw extruders respectively; The barrel of the single-screw extruder is divided into a first zone, a second zone, a third zone, a fourth zone and a fifth zone with different temperatures along the material flow direction; The temperature of the first zone is 160-170°C; The temperature of the second zone is 165-175°C; The temperature of the third zone is 170-180°C; The temperature of the fourth zone is 180-190°C; The temperature of the fifth zone is 175-185°C; The temperature of the transverse stretching is 120-130°C; The stretching ratio of the transverse stretching is 7 to 10; The longitudinal stretching temperature is 110-120°C; The stretching ratio of the longitudinal stretching is 4-6.

8. A high barrier and puncture resistant polyethylene composite film prepared by the method for preparing a high barrier and puncture resistant polyethylene composite film according to any one of claims 1 to 7, characterized in that: The high barrier and puncture-resistant polyethylene composite film comprises a substrate layer, a barrier layer and a puncture-resistant layer stacked in sequence; The substrate layer comprises metallocene polyethylene, linear low-density polyethylene, low-density polyethylene, a plasticizer, an antioxidant, a lubricant and an ultraviolet absorber; The barrier layer comprises high-density polyethylene, modified montmorillonite, modified nanocellulose, a plasticizer, a dispersant and a lubricant; The puncture-resistant layer comprises high-density polyethylene, maleic anhydride grafted ethylene-octene copolymer, maleic anhydride grafted polyethylene, modified boron nitride, a plasticizer, a dispersant and a lubricant.

9. The high barrier and puncture resistant polyethylene composite film according to claim 8, characterized in that: The thickness of the substrate layer is 10-20 μm; The thickness of the barrier layer is 20-30 μm; The thickness of the anti-puncture layer is 20-30 μm; The total thickness of the high barrier and puncture-resistant polyethylene composite film is 60-80 μm.

10. The high barrier and puncture resistant polyethylene composite film according to claim 8, characterized in that: The substrate layer comprises the following components in parts by weight: 50-60 parts of metallocene polyethylene; Linear low density polyethylene 15-25 parts; 10-20 parts of low-density polyethylene; 3~5 parts of plasticizer; 0.5~1.5 parts of antioxidant; Lubricant 0.8~1.2 parts; 0.3~0.8 parts of UV absorber; The barrier layer comprises the following components in parts by weight: High-density polyethylene 70-80 parts; Modified montmorillonite 12-15 parts; 4-6 parts of modified nanocellulose; 2~5 parts of plasticizer; Dispersant 1~3 parts; Lubricant 0.8~1.2 parts; The puncture-resistant layer comprises the following components in parts by weight: High-density polyethylene 75-85 parts; 5-6 parts of maleic anhydride grafted ethylene-octene copolymer; Maleic anhydride grafted polyethylene 3-4 parts; Modified boron nitride 2-5 parts; 2~5 parts of plasticizer; Dispersant 1~3 parts; Lubricant 0.8~1.2 parts.

11. The high barrier and puncture resistant polyethylene composite film according to claim 8, characterized in that: The ultraviolet absorber is any one of UV-531, UV-326 or UV-234 or a combination of at least two thereof; The antioxidant is any one of antioxidant 1010, antioxidant 1076, antioxidant 626, and antioxidant 168, or a combination of at least two thereof; The dispersant is any one of liquid paraffin, silicone oil, and ethylene glycol, or a combination of at least two thereof; The lubricant is any one of stearic acid, zinc stearate, and calcium stearate, or a combination of at least two thereof; The plasticizer is any one of glycerol, epoxidized soybean oil, and paraffin oil, or a combination of at least two of them.

12. Use of the high barrier and puncture resistant polyethylene composite film according to any one of claims 8 to 11 in livestock and poultry medicine packaging.